Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgk65 previousDOI: 10.5281/zenodo.3830951 shortDOI: 10/ghgk65 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3830951 10.5281/zenodo.3830951 10.53832/edtechhub.0030 10/ghgk65 2339240:2AU72ZG2 2339240:3DWURGVT 2339240:KMTF4A22 2339240:L86PMYJ2 2339240:PRSHWWK5 2405685:4TKSDH2I 2405685:97JHVZU9 2405685:GUJ3TBS3 2405685:NA8X7J9C 2405685:S3EKNHHG 2405685:XGAFJNAD 4656463:PU6FSTAF
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Verna Lalbeharie joins EdTech Hub as incoming Executive Director - Hub, EdTech (EdTech Hub, 2021)
We are excited to announce that Verna Lalbeharie is joining EdTech Hub as the incoming Executive Director. A native of South Africa, now living in North Carolina (USA), Lalbeharie brings not only 25 years of EdTech expertise to the role, but also a career-spanning commitment to evidence-building in education technology to create a more equitable future for all students. “When…
KerkoCite.ItemAlsoKnownAs: 2405685:GWTBTPXG
Keywords: _EdTechHub_Output

Highlights from EdTech and Covid-19: Lessons learned, future plans - Team, EdTech Hub (EdTech Hub, 2021)
On March 2nd EdTech Hub brought together education leaders, including teachers, program managers and policymakers, to reflect on a year of EdTech and Covid-19, discuss the lessons learned so far and consider how we can prepare for the future. Over 200 people joined from around the world for a lively and thought-provoking discussion. Speakers included: Helen Grant MP, UK Prime…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707919 2405685:UKK52XU7
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The EdTech Hub’s approach to amplifying impact through engagement – The EdTech Hub - Jamieson Eberhardt, Molly (EdTech Hub, 2019)
If you have spent time working in the education sector, you’ll know that even marginal gains are worthy of celebration. Those of us involved in launching the EdTech Hub know this well — from our experience as teachers, researchers, advisers, programme implementers, and civil servants. Nevertheless, we have the ambition to help accelerate progress toward quality education at an unprecedented rate. We of course know that sustainable change often takes time, and we respect hard-earned marginal gains. But what we’re really after is improvement in education outcomes at a pace that matches the urgency of the problem — think millions of children receiving quality education within a decade, not in decades.
shortDOI: 10/ghgngr KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906791 10/ghgngr 2405685:AGB565DF 2405685:MUPWVYW6
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:FQKKVE4W 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Summary: EdTech in Cambodia - A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Cambodia. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817714 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1038 ZenodoArchiveConcept: 12817713
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech for Learners With Hearing and Visual Impairments - A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Hearing and Visual Impairments produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819042 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1043 ZenodoArchiveConcept: 12819041
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819000 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1042 ZenodoArchiveConcept: 12818999
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Vietnam - A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12818950 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1041 ZenodoArchiveConcept: 12818949
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Lao People's Democratic Republic - A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Lao People's Democratic Republic. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817771 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1039 ZenodoArchiveConcept: 12817770
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Timor-Leste - A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817786 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1040 ZenodoArchiveConcept: 12817785
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech for Learners With Cognitive and Learning Disabilities - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Nimra, Afzal (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Cognitive and Learning Disabilities produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819139 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1045 ZenodoArchiveConcept: 12819138
Keywords: _r:AddedByMyEducationEvidence

EdTech Hub: Resources from other organisations - EdTech Hub (EdTech Hub, 2020)
Response efforts and collated resources Global Partnership for Education (GPE)’s response and resources INEE (Inter-Agency Network for Education in Emergencies) collated resources organised by theme COVID-19 ICT4E resources from mEducation Alliance members UNESCO’s response to COVID-19 including information about distance learning tools and national platforms UNHCR’s guidance on distance learning World Bank resources to help […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707760 2339240:6Q943EP5 2405685:Y76SNV85
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803111 10.53832/edtechhub.0075 2339240:XBN27377 2405685:674LJ8EY 2405685:EW94QPAA
Keywords: _r:AddedByZotZen

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707884 2339240:6XDHWICN 2405685:7FQR6GZK 2405685:Y22H6PQD
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

The EdTech Hub’s Helpdesk and COVID-19: Demand-driven advice (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. With more than 1.5 billion children now affected by school closures, ministries of education and decision-makers around the world are urgently in need of fast, evidence-based, context-specific advice about out-of-school learning. Teachers, caregivers, parents and policymakers are tirelessly working to ensure that learning doesn’t stop. Faced with one of the…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707475 2405685:666VVKWG 2405685:AFE9INVN
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

An inclusive approach to searching for evidence on EdTech in low- and middle- income countries - Brugha, Meaghan (EdTech Hub, 2020)
A blog post by Meaghan Brugha and Katy Jordan. A searchable database The EdTech Hub has undertaken a large-scale search for publications on technology use in education in low- and middle- income countries. During this process, we created an internal research database. This is searchable through the use of a variety of filters, such as …
EdTechHub.Source: <this> EdTechHub.Source: 2405685:BGLPB3AG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911079 2129771:86J5A5RJ 2405685:6TX2RFBC 2405685:BGLPB3AG
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoODE

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5032936 10.5281/zenodo.5142392 10.53832/edtechhub.0094 2405685:G9DHSZ57 2405685:HL6BNMQZ
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessey, Sarah; Jordan, Katy; Wagner, Daniel; EdTech Hub Team (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:P8FGXBPB 2405685:F8WM8674
Keywords: ⛔ No INSPIRE recid found

Summary: EdTech for Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Out-of-School Children and Youth produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _r:AddedByMyEducationEvidence

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4699337 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4699337 2339240:MQFC486E 2339240:YAXCDGIK 2405685:3GQXS67C 2405685:Q9F2PISN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Problem Analysis. A Global Public Good produced by the EdTech Hub - Hennessy, Sara; Jordan, Katy; Haßler, Björn; Hollow, David; Brugha, Meaghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (EdTech Hub, 2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
EdTechHub.Copy: 2129771:9VXUZISD EdTechHub.Copy: 2129771:ADGISTZU EdTechHub.ThisIsNot: 2339240:2387P995 2339240:8RA9UD7W shortDOI: 10/ghgnfz KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2129771:56GZ7UBP 2129771:9VXUZISD 2129771:ADGISTZU 2129771:GYTVIZJV 2129771:MBZLFNDM 2339240:2387P995 2339240:65KP6SVQ 2339240:6FUA4SDV 2339240:85SBE7SC 2339240:8RA9UD7W 2339240:IXIRDBKK 2339240:STPRNPV3 2405685:BBQI3VSA 2405685:CMRISZHV 2405685:F6UAIKKN 2405685:QJTH2UXC 2405685:R88UVQZ7 503888:7EH7BANW 503888:PI9FLM7C
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4924787 10.53832/edtechhub.0131 2405685:D7JX8S7S
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14749795 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1089 ZenodoArchiveConcept: 14749794
Keywords: _r:AddedByMyEducationEvidence

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech in Malawi: A Rapid Scan - Rui, Yang (Tingting) (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but not exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Malawi. Keywords: Malawi, EdTech, Policy, ICT An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7314047 ZenodoArchiveConcept: 7314046 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7314047 10.53832/edtechhub.0152 10.53832/edtechhub.1024 2405685:99ZRGDBB 2405685:NMJMENAG
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10837295 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1018 ZenodoArchiveConcept: 10837294
Keywords: _r:AddedByMyEducationEvidence

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:XCJNWSVR XCJNWSVR
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Hub Research and Innovation to fulfill the potential of EdTech - Nicolai, Susan (EdTech Hub, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:3547DQJS
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Introducing the EdTech Hub’s programme for research in low-income countries – The EdTech Hub - Hennessy, Sara (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:A7H9CPGD A7H9CPGD
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Methodology for literature reviews undertaken by the EdTech Hub - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Sara Hennessy; David Hollow; Katy Jordan; Kevin Martin; Mary Murphy; Hannah Walker (EdTech Hub, 2019)
An output of the EdTEch Hub
EdTechHub.Copy: 2129771:3GKL5PCI EdTechHub.Copy: 2129771:L2EAYWTN shortDOI: 10/ghgnfq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352101 10.5281/zenodo.3595594 10/ghgnfq 2129771:3GKL5PCI 2129771:K4IV67YV 2129771:L2EAYWTN 2317526:NRY5DISC 2339240:LY57CR53 2339240:XNCNITQP 2405685:BMM3Z3CM 2405685:CEJDF5XI
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _dont_post_PDF; _yl:h; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4703718 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4703718 2405685:CDC2W7Q6 2405685:HVQVC8TU
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
EdTechHub.Copy: 2129771:NPLNWHCZ shortDOI: 10/ghgnfd KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906829 10/ghgnfd 2129771:NPLNWHCZ 2129771:XKQV2EDS 2405685:3IM8DBXI
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Open educational resources - EdTech Hub (EdTech Hub, 2020)
As part of our COVID-19 response, the EdTech Hub is collecting and facilitating access to open educational resources (OER). Open educational resources are teaching, learning and research materials that are made freely available for anyone to access and re-use. These documents are currently stored on Google Drive (no sign-in required). We will add additional distribution […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707762 2405685:8HVQCGY9 2405685:XFLWPJ5R
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14051241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1068 ZenodoArchiveConcept: 14051240
Keywords: _r:AddedByMyEducationEvidence

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118401 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1025 ZenodoArchiveConcept: 11118400
Keywords: _r:AddedByMyEducationEvidence

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10893092 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1020 ZenodoArchiveConcept: 10893091
Keywords: _r:AddedByMyEducationEvidence

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7336710 ZenodoArchiveConcept: 7336709 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7336710 10.53832/edtechhub.0136 2339240:4TCBX2GH 2405685:3QBCENK5 2405685:AWHK2L8L
Keywords: _r:AddedByZotZen

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987856 ZenodoArchiveConcept: 10987855 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1022 10.53832/edtechhub.1086 2405685:S4V6PXXU

Introducing the EdTech Hub Specialist Network - Dzinotyiweyi, Monica; Mullan, Joel (EdTech Hub, 2020)
What is the Specialist Network? We’re an international group of experts with substantial practical experience in developing and implementing education and EdTech programmes around the world. The Specialist Network allows the EdTech Hub to draw on a wide range of context-specific and subject-specific experience and expertise. We have a particular focus on supporting the Hub’s Helpdesk, providing additional capacity to…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708248 2405685:CK8F2SMX
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118414 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1026 ZenodoArchiveConcept: 11118413
Keywords: _r:AddedByMyEducationEvidence

Advancing evidence-based decision making in LMICs: Focus of EdTech Hub’s work - Hennessy, Sara (EdTech Hub, 2021)
This blog sets out the Hub’s aims and approaches to identifying appropriate and effective uses of EdTech that can potentially raise learning outcomes in low- and middle-income countries (LMICs). Research shows that EdTech offers immense potential, but sustainable and positive change at scale has largely proved elusive in practice – particularly for marginalised learners where we focus our work. To…
KerkoCite.ItemAlsoKnownAs: 2405685:33PABHJH 2405685:Q8R8G8WG
Keywords: _EdTechHub_Output

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11652091 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1032 ZenodoArchiveConcept: 11652090
Keywords: _r:AddedByMyEducationEvidence

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

What you can expect from the future EdTech Hub website (EdTech Hub, 2020)
The EdTech Hub had just finished a seven-month planning phase when COVID-19 hit. A profound sense of urgency swept over us. We realized that the planning we had done for a gradual ramp-up was now feeling insufficient to fulfill our mission, given the new global reality of kids being away from school, and the potential for EdTech to help. Our…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707862 2405685:RRQSDQ99
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Equality of Usage of Personalised Learning Software: Key Findings from EdTech Hub and EIDU’s Sandbox in Kenya - Rahman, Asad; Tanveer, Rabia; Olwala, Tess; Musungu Ongadi, Allan; Freidberg, Aidan; Munialo, Indrah (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14525520 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1081 ZenodoArchiveConcept: 14525519
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

What we learnt in the Sandbox between onebillion, VSO Malawi and EdTech Hub (Sprint Review Draft) - Dinham, Nat; Plaut, Daniel; Rahman, Asad; Schmit, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4959811 2405685:M78SQRBW
Keywords: _EdTechHub_Output; _MELA_seen; _comingsoon; _r:AddedByZotZen

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4701259 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4701259 2339240:K42SWARR 2405685:DGECLZII 2405685:J83BVHG6 2405685:UXWEBRCC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Demand-Driven Evidence Delivery and Uptake: Reflections on the Edtech Hub Helpdesk - Jordan, Katy; Thakrar, Jayshree; Patel, Prachi; Ramesh Vasudevan, Sharanya; Coflan, Caitlin; Thang, Sarah; Myers, Christina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13736013 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1056 ZenodoArchiveConcept: 13736012
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Pakistan: A Rapid Scan - Baloch, Imdad; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, Pakistan. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652137 previousDOI: 10.5281/zenodo.3911655 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3911655 10.5281/zenodo.3911655 10.53832/edtechhub.0035 2339240:6WTP2GZS 2339240:WU54X4PB 2405685:89ZSBKU4 2405685:FIQDEKCI 2405685:S4IE8XC8 2405685:V88HMUZ2
Keywords: C:Pakistan; F: Country scan; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgnd3 previousDOI: 10.5281/zenodo.3903213 shortDOI: 10/ghgnd3 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3903213 10.5281/zenodo.3903213 10.53832/edtechhub.0038 10/ghgnd3 2339240:4GMNADXW 2339240:NJVI79X2 2339240:VJKBU72Y 2405685:C5MWWQI2 2405685:D25NXEFY 2405685:NNCCIL5M 2405685:RHJ9EDQH 4656463:K7AIYRDP
Keywords: C:Sierra Leone; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Rwanda: A Rapid Scan - Kimenyi, Eric; Chuang, Rachel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Rwanda. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert
ZenodoArchiveID: 5652133 previousshortDOI: 10/ghgk7b previousDOI: 10.5281/zenodo.3910001 shortDOI: 10/ghgk7b KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3910001 10.53832/edtechhub.0036 10/ghgk7b 2339240:4B5GHNVX 2339240:6JUV7UTX 2339240:AHC7BX8D 2405685:5M49KR46 2405685:R6VF76MR 2405685:TYBTWI8K 2405685:XACNVSXA 2405685:ZV2XDVCB 4656463:A4BUGJYC
Keywords: C:Rwanda; F: Country scan; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech in Jordan: A Rapid Scan - Khalayleh, A.; Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, in Jordan. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652134 previousshortDOI: 10/ghgk66 previousDOI: 10.5281/zenodo.3911128 EdTechHub.Source: 2405685:XCMYPX8N EdTechHub.Source: <this> shortDOI: 10/ghgk66 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3911128 10.5281/zenodo.3911128 10.53832/edtechhub.0031 10/ghgk66 2129771:2T8DG8CP 2129771:8L3DWY74 2339240:C6U7EP9U 2339240:DN2PWAGF 2405685:LY4IVJEZ 2405685:NB8YWJYP 2405685:XCMYPX8N
Keywords: C:Jordan; F: Country scan; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Tanzania: A Rapid Scan - Groeneveld, Caspar; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private-sector partnerships, and the digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Tanzania. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652136 previousshortDOI: 10/ghgnd4 previousDOI: 10.5281/zenodo.3911643 shortDOI: 10/ghgnd4 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3911643 10.5281/zenodo.3911643 10.53832/edtechhub.0039 10/ghgnd4 2339240:2TKLQMKH 2339240:34IT889J 2339240:3UYWE57M 2339240:KMUFUI9L 2339240:MAIH68ES 2405685:4LWXXRCJ 2405685:5E4ZNE5G 2405685:F529QI2E 2405685:FCPCJFJ4 2405685:K76239FV 2405685:PW7BBS8G 2405685:UN3KMN7M 4656463:N2EMSCU6
Keywords: C:Tanzania; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Session 6: How do I ensure my EdTech investments are cost-effective? - Chuang, Rachel; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341519 ZenodoArchiveConcept: 7341518 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341460 10.5281/zenodo.7341519 10.53832/edtechhub.0140 2405685:CUFS8JJE 2405685:CWKPJR8R
Keywords: _r:AddedByZotZen

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341509 ZenodoArchiveConcept: 7341508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341509 10.53832/edtechhub.0139 2405685:NUTI6KUS 2405685:PPRW2NTQ
Keywords: _r:AddedByZotZen

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Consolidated Feedback on Tanzania Higher Education University Strategic Investment Plans - Adam, Taskeen; Koomar, Saalim; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk Response provides feedback on 15 Tanzania University Strategic Implementation Plans (USIPs) submitted to the Word Bank’s Higher Education for Economic Transformation Project (HEET). The feedback is intended to enhance and strengthen the plans provided by universities such that the USD 300 million is allocated and spent most effectively.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3986727 2129771:B5Z854HJ 2339240:IEATEWRY 2405685:7AFXFRPC
Keywords: Helpdesk Response; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; dode_eth-src-eth; dode_eth-trf2-dode

Call for ideas for EdTech responses to coronavirus (COVID-19) - EdTech Hub (EdTech Hub, 2020)
UPDATE: The call is now closed We’ve opened a sub-window in partnership with UNHCR for refugee related ideas that respond to COVID-19 school closures. Find full details here. Our call for ideas to respond to the learning emergency caused by COVID-19 school closures is now closed. We have been delighted and overwhelmed by the huge number […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707758 2405685:CZ9F7VZ2
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10599846 ZenodoArchiveConcept: 10599845 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1004 2339240:VBH94XQQ 2405685:DJRV7KZW
Keywords: _r:AddedByMyEducationEvidence

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7106003 ZenodoArchiveConcept: 7106002 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7106003 10.53832/edtechhub.0119 2405685:Y3SBIPF9 2405685:ZVX4DTXQ
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7003826 ZenodoArchiveConcept: 7003825 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7003826 10.53832/edtechhub.0118 2339240:3XB6YUXL 2405685:GXLAGDUM 2405685:RPR47JXT 2405685:ZXBB58KS
Keywords: _r:AddedByZotZen

EdTech Horizon Scan: Blockchain technology in education - Beoku-Betts, Iman; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking on a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This EdTech Horizon Scan examines the use of blockchain technology in education. Beginning with an overview of blockchain technology, the scan explains what blockchain technology is and how it works. The next section focuses on how blockchain technology can be used in education. In particular, it looks at the benefits of using blockchain technology for micro-credentialing and ownership of learning credentials, the transfer of credits and smart contracts, storing student credentials, identity verification and intellectual property protection. Section 4 gives a summary of the use of blockchain technology, noting the different challenges that may be associated with adopting blockchain technology into education systems. Section 5, gives real examples of the use of blockchain technology in education and different education institutions. Key words: blockchain; cryptography; data; decentralised database; digitalisation; education; micro-credentialing; smart contracting; student credentials; verification An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676491 10.5281/zenodo.6812384 10.53832/edtechhub.00101 10.53832/edtechhub.0101 2405685:94H68P58 2405685:S9XXPAHD 2405685:VJ84DKDF
Keywords: _r:AddedByZotZen

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7306712 ZenodoArchiveConcept: 7306711 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7306712 10.53832/edtechhub.0132 2405685:ACLTCQV2 2405685:XIIQ4FSE
Keywords: _r:AddedByZotZen

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4780972 2405685:4UQT8WRN 2405685:WWUQ7VRT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Decolonising EdTech: Unpacking Conceptual Frameworks. Writers Workshop 1 - Adam, Taskeen; Moustafa, Nariman (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7850804 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7850804 ZenodoArchiveConcept: 7850803
Keywords: _comingsoon; _r:AddedByZotZen

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4747475 2405685:RIPJWUDB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
ZenodoArchiveID: 4928926 PreviousDOI: 10.5281/zenodo.4747301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4928926 2339240:PXT8SGSZ 2405685:9P9W4I53 2405685:A2D9FVTA 2405685:C2579UKC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
ZenodoArchiveID: 3966976 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3966976 2129771:XMGQ4JQJ 2339240:L5RLM582 2339240:R72E853W 2405685:T2W7MU3K 2405685:U49W6LTF 2405685:ZI8PHKCC
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803107 10.53832/edtechhub.0076 2405685:CI5UZ5R4 2405685:HU5IFEK9
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5795656 10.53832/edtechhub.0079 2405685:5XBMPDX6
Keywords: _r:AddedByZotZen

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783101 2405685:MIQMEJK2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803101 10.53832/edtechhub.0077 2405685:VFV5SG9H
Keywords: _r:AddedByZotZen

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5654887 10.53832/edtechhub.0067 2339240:VNTPMCJQ 2339240:XLHSGBDA 2405685:FSVST5BF 2405685:HVDCZZVG 2405685:L5WPA5SN 2405685:YWENAQDF
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

EdTech call for ideas: What have we learned from the applications? (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. On 21st April, we launched a call for ideas for EdTech in responses to coronavirus and the lockdown of schools around the world. Three weeks later, we’ve taken a slice of the first 100 responses and analysed the data. Combining this with conversations our team is having every day with technologists and…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707827 2405685:NX2U4EMJ
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
previousshortDOI: 10/ghgngk previousshortDOI: 10/ghgngk previousDOI: 10.5281/zenodo.3631750 previousshortDOI: 10/ghgngk EdTechHub.Copy: 2129771:5EWDQDIA EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngk KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631750 10.53832/edtechhub.0013 10/ghgngk 2129771:5EWDQDIA 2339240:4KQKED7R 2339240:94ZP3EK4 2405685:978RP7D4 2405685:VM6NXYF3
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Social And Emotional Learning and EdTech: An Evidence Review - Kalifa, Damani (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5094331 2405685:FNJUHA6J
Keywords: _EdTechHub_Output; _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
previousshortDOI: 10/ghgngg previousshortDOI: 10/ghgngg previousDOI: 10.5281/zenodo.3631746 previousshortDOI: 10/ghgngg EdTechHub.Copy: 2129771:EHFUXJQC EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngg KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631746 10.53832/edtechhub.0011 10/ghgngg 2129771:EHFUXJQC 2129771:YHNWVMB3 2339240:94ZP3EK4 2339240:FIDI5TC2 2405685:39DIRNE9 2405685:HH3QKBIF 2405685:I3BV48CX 2405685:ITL9PIC3 2405685:K8BSWYFM 2405685:KF9F48ID 2405685:N68MMAPR 2405685:P5Y5GMFN 2405685:SC5NHA65 2486141:TAY7LNB6
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
ZenodoArchiveID: 3631748 previousshortDOI: 10/ghgngh previousshortDOI: 10/ghgngh previousDOI: 10.5281/zenodo.3631748 previousshortDOI: 10/ghgngh EdTechHub.Copy: 2129771:UEUAKMXJ EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngh KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631748 10.53832/edtechhub.0012 10/ghgngh 2129771:UEUAKMXJ 2339240:94ZP3EK4 2339240:E62J77SP 2339240:MM2SDXUM 2339240:S4UAH7Q3 2405685:3AV6MSKJ 2405685:DQWJLRN5 2405685:H9W2X3KM
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

A proposal for open educational resource adoption through a curriculum alignment hub - Chandra, Shivi (EdTech Hub, 2020)
In 2020, EdTech Hub began a collaboration with Learning Equality, a nonprofit organisation supporting the creation, adaptation, and distribution of Open Educational Resources (OER) in disconnected environments. The following post by Learning Equality’s Global Curriculum Specialist, Shivi Chandra, explores how individual efforts to address some of the challenges in adopting OER could become more powerful, receive recognition, and build upon…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707958 2339240:ZHJUIFM5 2405685:9QCBITED 2405685:UE5ASMRI
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Systems Research - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596889 ZenodoArchiveConcept: 5596888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0061 2405685:MDEEA895

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
ZenodoArchiveID: 4706000 previousDOI: 10.5281/zenodo.4706000 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3971656 10.5281/zenodo.4706000 10.53832/edtechhub.0029 2129771:YZIID28Y 2339240:7P4VDPLY 2339240:WYT4QCIW 2405685:85C5HVC7 2405685:I86XXKMH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Conseils pour l’introduction de la technologie en classe Liste de sources annotée - Allier-Gagneur, Zoé; Lwamba, Etienne (EdTech Hub, 2020)
Cette liste de sources annotée a pour but d’informer la prise de décisions des acteurs du domaine de l’éducation concernant l’introduction de technologies en classe dans les pays à revenu faible et intermédiaire. Cette liste est une introduction qui expose de façon informelle certains des conseils généraux que prodiguent souvent les experts de l’EdTech Hub.
ZenodoArchiveID: 3952001 previousDOI: 10.5281/zenodo.3952001 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952001 10.53832/edtechhub.0024 2339240:6H2ZA568 2405685:HDRVT5N4 2405685:PA2H8NGA
Keywords: F: Helpdesk response; LP: French; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
previousshortDOI: 10/ghgk6r previousDOI: 10.5281/zenodo.3884302 EdTechHub.Source: 2405685:6W2UWE89 EdTechHub.Source: <this> shortDOI: 10/ghgk6r KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3884302 10.53832/edtechhub.0041 10/ghgk6r 2129771:2MD2QL8K 2339240:7QEJ68RG 2405685:6W2UWE89 2405685:7HQN2HAD
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783017 2405685:89DPN3SP 2405685:EVSZNGMA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

A Case for a Systems Approach to EdTech - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651995 previousDOI: 10.5281/zenodo.4604769 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4604769 10.5281/zenodo.5651995 2339240:5JZ4FURY 2339240:5MG5JK99 2339240:8CEUGJ7E 2339240:N7XVM2BS 2339240:QL5LSA92 2339240:UIDN49MT 2405685:5HSPDN5N 2405685:AMGEVSIH 2405685:JMP2BJ2E 2405685:M8P5BVVK 2405685:ST8IBIUV 2405685:UR6CQL9K 2405685:VBZ4N4AM 2534378:PDNLLG9Y 4656463:RA69ZQLB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651932 previousDOI: 10.5281/zenodo.4917221 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4917221 10.5281/zenodo.5651932 2405685:V6UCUGBZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech and Covid-19: 10 things to know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709698 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2339240:ZD45QNVV 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:FMY4DMRL 2405685:VJ488Z7L
Keywords: _EdTechHub_Output; _GS:not_indexed; _cover:v3; _r:CopiedFromEvLib; _zenodoETH

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech for Learners with Disabilities in Primary School Settings in LMICS: A Systematic Literature Review - Lynch, Paul; Singhal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
This systematic literature review was guided by the overarching aim of establishing the categories of EdTech that may be appropriate to support the learning of children with disabilities aged 4–12 years in low-and middle-income countries. A critical review of the published literature was deemed essential as the field of disability and EdTech (mirroring larger trends in disability and educational research) has remained dominated by anecdotal commentaries and strong personal assertions, but substantiated by little evidence. In framing the review we drew on a dual model of access which provides a helpful lens into how EdTech can support a learner’s development trajectory across different interventions (e.g. learning to read Braille or sign language), targeted educational outcomes, inclusive practices and suitable accommodations in different educational settings. This approach is underpinned by a human rights agenda, as articulated in the UN Convention for the Rights of Persons with Disabilities (CRPD) and the Sustainable Development Goals (SDGs) which demand fair and equal access to education for all children and young people. They are also concerned, though, that an individual child/young person should have agency, self-determination and independence. Article 2 of the CRPD unambiguously recognizes that reasonable accommodation is vital in enabling persons with disabilities to enjoy and exercise their rights on an equal basis with others.
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4348995 10.5281/zenodo.4348995 2339240:6VEXVUL7 2339240:BAU4D8ER 2339240:PAABA4B7 2339240:RHJJP4E2 2339240:TWQV2AGE 2339240:Z4FHRC9L 2405685:7IEM9MCP 2405685:88MZ92YX 2405685:ATYBHAIH 2405685:DGRQM9XQ 2405685:KKZ3ET5W 2405685:KL56SD42 2405685:VZNCHGEG 2405685:XJ42VUQG 2534378:3A5TU66J
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
ZenodoArchiveID: 4709700 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709700 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Using EdTech to Support Effective Data Monitoring: A Curated Resource List. - Koomar, Saalim; Blest, Harriet (EdTech Hub, 2020)
This list curates resources on the use of EdTech to support the effective monitoring of educational outcomes, such as learning, reporting, and attendance. Resources shared are both tools and initiatives that can be adapted to support effective educational monitoring.
ZenodoArchiveID: 4762325 previousDOI: 10.5281/zenodo.4762325 PREV_DOI_NOT_ETH: 10.5281/zenodo.4091396 shortDOI: 10/ghgng6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407517 10.5281/zenodo.4762325 10/ghgng6 2339240:C9LP4Y2Z 2339240:EKNZDSVU 2339240:GMJF38V5 2339240:MZKWF23D 2339240:QJX4VXGR 2405685:7I4HVAV2 2405685:884LRL46 2405685:ANHT4I3J 2405685:FS4CMYUB 2405685:RV39YP9Q 2405685:WCYEVIJU 4656463:K7HMFX7H
Keywords: C:Mozambique; ES:Educational data; ES:Monitoring and evaluation; F: Helpdesk response; L:Low-level foundational skills; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Evidence Coaching Handbook - Rahman, Asad (EdTech Hub, 2024)
This handbook captures EdTech Hub's approach to providing evidence coaching on the EdTech Hub Evidence-Led Entrepreneurship Course. Individuals and organisations who support EdTech entrepreneurs to scale their products impactfully (e.g., accelerators, entrepreneurship programmes, funders) can all provide evidence coaching to entrepreneurs. This Handbook is for anyone working within an EdTech startup, or an entrepreneur who wants to better apply evidence to key decisions. By sharing EdTech Hub’s approach and process for evidence coaching, we hope to nurture a more evidence-led EdTech entrepreneurship ecosystem, leading to more EdTech products that scale sustainably, and help children to read, write, and count. The Handbook contains EdTech Hub’s five-step process for generating and applying evidence as a startup, with specific tools we used along the way. The process is a guide for others to adapt and tailor to their unique context and challenges. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255915 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1051 ZenodoArchiveConcept: 13255914
Keywords: _r:AddedByMyEducationEvidence

Sandboxes: our approach to systemic experimentation - Simpson, Lea (EdTech Hub, 2020)
What’s a sandbox you ask? First in the series, this blog explains what you need to know about the Hub’s approach to experimentation and innovation.
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:N8IVIWTD 2339240:UM8QDJVD 2405685:EU5H44PP 2405685:T22QNFKK 2405685:XZLUI8BE
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Sandboxes: Testing the strategy in Malawi - Carter, Alice (EdTech Hub, 2020)
Written by Alice Carter This is the second in this series about our sandboxes. If you haven’t already, read about our approach to experimentation. Across the Hub, we’re proponents of using our tools and approaches on our own thinking. For innovation, that meant testing the assumptions we were making about how and if the sandboxes …
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2405685:785EE55K
Keywords: C:Malawi; F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
ZenodoArchiveID: 4706019 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706019 2339240:D85SY35R 2405685:SMLIMS2X
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Jordan’s EdTech response to COVID-19 - Al-Hindawi, Hind; Hashem, Lina (EdTech Hub, 2020)
ZenodoArchiveID: 4706057 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706057 2339240:7DDCIKY9 2339240:P8XVRD6S 2405685:BTX9XW3J 2405685:KNCXGVW3 2405685:XFBMF3QV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Tackling coloniality in EdTech: Making your offering inclusive and socially just - Adam, Taskeen; Moustafa, Nariman; Sarwar, MoizzaBinat (EdTech Hub, 2022)
On 29 June 2022, Bertha Centre, EdTech Hub, Open Development & Education and the Overseas Development Institute (ODI) presented a workshop on Tackling Coloniality in EdTech. The workshop was hosted by Ntombini Marrengane (Bertha Institute). This slide deck shares the resources and activities used at the workshop, in the hope that it inspires others to host similar workshops that critically reflect on how coloniality can be embedded in EdTech designs, projects, programmes, processes, structures, values, knowledge systems, and philosophies.
ZenodoArchiveID: 7612943 ZenodoArchiveConcept: 7612942 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7612943 10.53832/edtechhub.0147 10.53832/edtechhub.0150 2405685:3QV8PAED
Keywords: _r:AddedByZotZen

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15352737 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1112 ZenodoArchiveConcept: 15352736
Keywords: _r:AddedByMyEducationEvidence

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Monitoring Hybrid Learning: A Short Guide - UNICEF; EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5826252 10.53832/edtechhub.0072 2405685:NHNPTFBW
Keywords: F: Helpdesk response; _r:AddedByZotZen

Operational Guide for Monitoring Hybrid Learning Delivery Toward Long-Term System Strengthening and Resilient Education Systems - UNICEF; EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5826264 10.53832/edtechhub.0074 2405685:P59N3JKT
Keywords: F: Helpdesk response; _r:AddedByZotZen

Helping you find and compare EdTech tools (EdTech Hub, 2020)
We’re excited to publish the first version of a tool to help you find and compare EdTech tools. The EdTech Hub’s mission is to increase the use of evidence to inform decision-making about education technology. Right now, our focus is on helping you think about whether and how EdTech can help you respond to the challenges of the school closures…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707844 2405685:M5H8WQNZ
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Call for Research Proposals: EdTech responses to Covid-19 (EdTech Hub, 2020)
EdTech Hub is excited to launch a call for proposals to fund a series of small research projects (3-6 months) related to Covid-19 response and recovery using educational technology (EdTech). The selected research projects will investigate the practical application of EdTech, generate primary research, and develop recommendations which aim to be useful during Covid-19 response, recovery, and beyond. We see…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707484 2405685:QE24K5YV
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Why the COVID Crisis Is Not EdTech’s Moment in Africa (EdTech Hub, 2020)
This blog was originally posted on the Center for Global Development blog with data used from the EdTech Hub’s database of interventions. Our database, which was initially limited to sub-Saharan Africa, now has a global scope. As the blog suggests, there is a need to increase the database’s representation of interventions in other regions. Please add your EdTech intervention to…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707833 2405685:2AW76Y8P
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Behaviour change key principles for EdTech | MASTER framework - Rahman, Asad; Carter, Alice; Wambûi Kuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries, to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool aims to help you get started with ways to design for innovation behaviours or mindsets and make them stick. Keywords: behavioural change; behavioural design; behavioural innovation; EdTech; innovation; sandbox; intervention design An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245959 ZenodoArchiveConcept: 7245958 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245959 10.53832/edtechhub.0129 2339240:UURNQTLM 2405685:6SXI2PS9 2405685:BT283J6U 2405685:KEFXIABC
Keywords: _r:AddedByZotZen

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
ZenodoArchiveID: 4706036 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706036 2339240:CB8D4LUQ 2339240:METE88UD 2339240:MK55NVDC 2339240:Z3EF9Q75 2405685:3XIBJD8G 2405685:3Y33YNL3 2405685:8JZVGC6W 2405685:HBXKVKMA 2405685:QJ783WH5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694602 ZenodoArchiveConcept: 10694601 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080734 10.53832/edtechhub.1015
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTechTools Relaunched with TVET Resources - EdTech Hub; Generation Unlimited (EdTech Hub, 2021)
EdTechHub, Generation Unlimited (GenU), UNESCO and UNESCO-UNEVOC have joined forces to relaunch EdTechTools (formerly the Tools Database): a global repository of education technology tools and platforms designed to help decision makers at all levels in the global education and training community find resources that facilitate and support remote learning. More than a year after the world experienced an education disruption…
KerkoCite.ItemAlsoKnownAs: 2405685:HNAI38V8
Keywords: _EdTechHub_Output

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14260074 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1078 ZenodoArchiveConcept: 14260073
Keywords: _r:AddedByMyEducationEvidence

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4540204 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 10.5281/zenodo.4540204 2339240:26GYDUTU 2339240:2Q9AWGM3 2339240:IQ36IBT8 2339240:MDUWMNQ5 2339240:P9XQBBQC 2405685:856UY54Y 2405685:CZZ5WHT7 2405685:P9T68ACJ 2405685:UGZDH4LB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

Conceptual Framework for Monitoring Hybrid Learning Delivery Toward Long-Term System Strengthening and Resilient Education Systems - UNICEF; EdTech Hub (UNICEF, EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5826262 10.53832/edtechhub.0073 2405685:3EQU9ZAN
Keywords: F: Helpdesk response; _r:AddedByZotZen

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Using EdTech in Response to Climate Emergencies in Pakistan: A Policy Note - Hayat, Amal (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15851578 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1129 ZenodoArchiveConcept: 15851577
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

EdTech and Covid-19: the story so far - Gould, Briony (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4899740 2405685:IWGMZ8QI
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
ZenodoArchiveID: 5652121 previousZenodoArchiveID: 3941727 previousDOI: 10.5281/zenodo.3941727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3941727 10.53832/edtechhub.0028 2129771:KLLMDHKK 2339240:Y5Z46TRU 2405685:2B8SH5S3 2405685:K7JDL4IL
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117635 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1047 ZenodoArchiveConcept: 13117634
Keywords: _r:AddedByMyEducationEvidence

Summary: Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Afzal, Nimra; Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1046 ZenodoArchiveConcept: 13117630
Keywords: _r:AddedByMyEducationEvidence

EdTech for Marginalized Learners in Southeast Asia - Perspectives from Funders and Providers on Priorities, Design, Investment and Scaling Considerations - Chrisani, Aprillia; Honda, Delanie; Jayasinghe, Neema; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15387632 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1117 ZenodoArchiveConcept: 15387631
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14172051 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1069 ZenodoArchiveConcept: 14172050
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117643 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1049 ZenodoArchiveConcept: 13117642
Keywords: _r:AddedByMyEducationEvidence

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117639 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1048 ZenodoArchiveConcept: 13117638
Keywords: _r:AddedByMyEducationEvidence

Harnessing EdTech for Neurodivergent Learners in LMICs - Aida, Layachi; Daniel, Plaut (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15737188 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1124 ZenodoArchiveConcept: 15737187
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech in Nigeria: A Rapid Scan - Dele-Ajayi, Opeyemi; Taddese, Abeba (EdTech Hub, 2020)
previousshortDOI: 10/ghgk69 previousDOI: 10.5281/zenodo.3911651 shortDOI: 10/ghgk69 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911651 10.53832/edtechhub.0034 10/ghgk69 2339240:4SKXJ887 2405685:ED7RBJHG 2405685:VSMMBMQE
Keywords: C:Nigeria; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Exploring Teacher Digital Skills and Literacy Competencies: A curated list of frameworks and resources to inform UNICEF Thailand - Flam, Rebekka; Upadhyay, Arjun; Thang, Sarah (EdTech Hub, 2025)
This report was developed in response to a request from UNICEF Thailand for a curated list of digital skills and literacy frameworks designed for teachers. It reviews and compares 16 global, regional, and national frameworks to inform the development or adaptation of teacher-specific training and materials in Thailand. Key insights include the multidimensional nature of digital literacy, the central role of teacher development, and the alignment of learner-centred approaches with competency-based education (CBE). The report concludes with practical recommendations for policymakers, educators, and practitioners in Thailand involved in designing or implementing digital skills and literacy frameworks. Keywords: Digital literacy; digital skills frameworks; teacher competencies; Thailand; Southeast Asia; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15499486 ZenodoArchiveConcept: 15499485 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1120 2405685:I2DINV6N
Keywords: _r:AddedByMyEducationEvidence

EdTech in Kenya: A Rapid Scan - Otieno, J.; Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private-sector partnerships, and the digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Kenya. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgk67 previousDOI: 10.5281/zenodo.3909977 shortDOI: 10/ghgk67 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3909977 10.5281/zenodo.3909977 10.53832/edtechhub.0032 10/ghgk67 2339240:APCX6FZF 2339240:GCTJ3BGT 2339240:L7QHYF3W 2339240:T4YIDZJ7 2339240:TAJM927Q 2405685:7JQHE3IU 2405685:C4PSATWV 2405685:CQ5E3ESF 2405685:DKEN8UKZ 2405685:X257CWNC 2405685:ZPITMJJ3
Keywords: C:Kenya; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech and COVID-19 response - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (The EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
ZenodoArchiveID: 5652040 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652040 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:QWFICPBX 2405685:SXDQAPB6 2405685:TSDUZKH9
Keywords: _DOILIVE; _EdTechHub_Output; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; ⛔ No DOI found

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:JMFNCMP8 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:S5PCWMRP 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7 4804264:EZB37W4S
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13766685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1059 ZenodoArchiveConcept: 13766684
Keywords: _r:AddedByMyEducationEvidence

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995637 ZenodoArchiveConcept: 14995636 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7997034 10.5281/zenodo.7997057 10.5281/zenodo.8401936 10.53832/edtechhub.1100 2405685:4MWP8553 2405685:5DJ69UTD
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Embracing EdTech: four critical questions answered through a rapid prototype programme on teachers’ professional development (TPD) - Sabbab, Salman; Shakil, Abdullah All; Alam, Faria (EdTech Hub, 2021)
Seventy-one teachers participating in the ‘Onneshon’ prototype were flooding the WhatsApp group with messages about the challenges and hiccups they were experiencing, either with watching the video content or with taking a quiz in the first two weeks. Problems were pouring in and so were solutions being innovated and offered through diverse channels. In the space of two weeks, the…
KerkoCite.ItemAlsoKnownAs: 2405685:ZWUKU2YL
Keywords: _EdTechHub_Output

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14648336 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1087 ZenodoArchiveConcept: 14648335
Keywords: Hide; _r:AddedByMyEducationEvidence

EdTech and Covid-19: lessons from around the world - Pellini, Arnaldo (EdTech Hub, 2021)
Arnaldo Pellini, Susan Nicolai, Moizza Binat Sarwar, Sam Wilson, Akanksha Bapna, Chris McBurnie, Adedoyin Adesina, Oladele Akogun, Ernest Ngabo, Hind Al-Hindawi, Ni Wayan Suriastini, Vollan Ochieng, Moses Ngware, Asma Rabi , Abdul Musawir, Clement Sefa-Nyarko, Edem Agbe , Rabia Tabassum, Amna Zaidi, Jeroen Groenewegen, Harish Doraiswamy, Sudhansu Sharma, Liangdi Xu In this blog we summarise four takeaways from a reflection…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707940 2339240:PAIL2F6F 2405685:27J8ETI9 2405685:G34FUWKA
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230830 ZenodoArchiveConcept: 14230829 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1061 10.53832/edtechhub.1075
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Guide pour les utilisateurs de la tablette et de la plateforme Formation À Distance - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a practical guide for users of a tablet for the distance learning platform (FAD), specifically for 2000 primary teachers in Madagascar. It covers: Tablet Basics: How to use the tablet, buttons, screen, touch controls, navigation, and settings. Accessories: Information on the solar charger / power bank and mini-speaker. Communication: Instructions on making calls, sending SMS and emails, and accessing the internet. Applications: Guides for using applications for training content and exercises. Online Platform: Instructions for accessing and using the Moodle online platform for assessments and resources. Tablet Care: Tips for protecting the tablet and optimizing battery life. The guide is intended for beginners and provides step-by-step instructions with illustrations. It also includes a list of abbreviations and acronyms. Keywords: teacher professional development; Madagascar; Moodle; tablet; user guide Ceci est un guide pratique destiné aux utilisateurs d’une tablette pour la plateforme d’apprentissage à distance (FAD), spécifiquement conçu pour 2000 enseignants du primaire à Madagascar. Il couvre : Bases de la tablette : Utilisation de la tablette, boutons, écran, commandes tactiles, navigation et paramètres. Accessoires : Informations sur le chargeur solaire/batterie externe et le mini-haut-parleur. Communication : Instructions pour passer des appels, envoyer des SMS et des e-mails, et accéder à Internet. Applications : Guides d’utilisation des applications pour les contenus de formation et les exercices. Plateforme en ligne : Instructions pour accéder et utiliser la plateforme Moodle pour les évaluations et les ressources. Entretien de la tablette : Conseils pour protéger la tablette et optimiser l’autonomie de la batterie. Ce guide est destiné aux débutants et propose des instructions pas à pas avec illustrations. Il comprend également une liste d’abréviations et d’acronymes. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les utilisateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230784 ZenodoArchiveConcept: 14230783 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1066 10.53832/edtechhub.1073
Keywords: _r:AddedByMyEducationEvidence

EdTech in Vietnam: A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. This report was originally written in March 2024. It is based primarily on desk research, with quality assurance provided by country experts at Southeast Asian Ministers of Education Organization (SEAMEO) centres. Keywords: out-of-school children and youth; digital education; Southeast Asia; girls’ education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11445854 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1031 ZenodoArchiveConcept: 11445853
Keywords: _r:AddedByMyEducationEvidence

EdTech for learners with disabilities: urgent need to focus on access, engagement and learning outcomes - Singal, Nidhi; Lynch, Paul; Kaye, Tom; Francis, Gill (EdTech Hub, 2021)
The current approaches to providing high quality learning experiences to learners with disabilities in low and middle-income (LMICs) countries requires radical rethinking. To date, significant numbers of learners with disabilities are not enjoying the benefits of barrier-free and meaningful engagement with the school curriculum in order to reach their potential. Appropriately matched technology to learner needs – in terms of…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4728168 2405685:6QJYLAD7 2405685:BZDFHTPM
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230806 ZenodoArchiveConcept: 14230805 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1062 10.53832/edtechhub.1074
Keywords: _r:AddedByMyEducationEvidence

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and students could access and use…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707888 2405685:E2KWWHCK 2405685:LND4UENT
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230731 ZenodoArchiveConcept: 14230730 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1035 10.53832/edtechhub.1071
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230760 ZenodoArchiveConcept: 14230759 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1058 10.53832/edtechhub.1072
Keywords: _r:AddedByMyEducationEvidence

Hello and Welcome to the Sandbox - Simpson, Lea; Carter, Alice; Rahman, Asad (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5123366 2405685:CQQURC65
Keywords: _EdTechHub_Output; _r:AddedByZotZen

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995952 ZenodoArchiveConcept: 14995951 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7303773 10.53832/edtechhub.1101 2405685:RMJK6G6Q
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Sustainable Solutions to Rural Girls’ Education: A Rapid Evaluation of Lyra in Africa’s Green Hostels - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7858344 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7858344 ZenodoArchiveConcept: 7858343
Keywords: _r:AddedByZotZen

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

EdTech companies in Sub-Saharan Africa - EdTech Hub (Airtable, 2020)
Explore the "EdTech companies in Sub-Saharan Africa (see https://tabsoft.co/338AGht for visuals)" view on Airtable.
KerkoCite.ItemAlsoKnownAs: 2339240:J7JR8C2K 2405685:64SY5VBN

The Use of Technology in the CPD Implementation Plan in Tanzania - Adam, Taskeen; El-Sefary, Yomna; Haßler, Björn; Khalayleh, Abdullah; Kremeia, Adam; Proctor, Jamie; Mtebe, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4665846 2405685:N5HMII3R
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Outputs Register: The Impact of GIS-Supported Teacher Allocation in Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman; Frazer, Madleen Madina (EdTech Hub, 2023)
EdTech Hub, Fab Inc, and the Education Workforce Initiative have produced the outputs listed in this document as part of the EdTech Hub-commissioned research project on ‘GIS-supported teacher allocation in Sierra Leone’. This research project began in January 2022. This document lists all outputs produced under this project. All outputs are available to the public via the EdTech Hub Evidence Library. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396199 10.5281/zenodo.6472492 10.53832/edtechhub.0089 10.53832/edtechhub.0163 10.53832/edtechhub.0164 2129771:3J4TNGDZ 2339240:QAKR5YM8 2405685:9XJGEX5Z 2405685:NNBEHF4D 2405685:WXBISTFE
Keywords: Author:OpenDevEd; HLR3; _C:Sierra Leone SLE; _r:AddedByZotZen

EdTech and Covid-19: 10 things to know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709698 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2339240:ZD45QNVV 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:FMY4DMRL 2405685:VJ488Z7L
Keywords: _EdTechHub_Output; _GS:not_indexed; _cover:v3; _r:CopiedFromEvLib; _zenodoETH

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5813529 10.53832/edtechhub.0084 2405685:DPWSAA9Z
Keywords: _r:AddedByZotZen

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396237 10.53832/edtechhub.0086 2405685:CVS2WZC3 2405685:FVSQD8MB
Keywords: F: Helpdesk response; _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Sandboxes: My experience participating in the sandbox alpha - Kumasewera, Pilirani (EdTech Hub, 2020)
This is the third in this series about our sandboxes. If you haven’t already, read about our approach to experimentation and how we tested our sandbox strategy out in Malawi.
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2405685:CE3XH7JY
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7754059 ZenodoArchiveConcept: 7754058 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521858 10.5281/zenodo.7754059 10.53832/edtechhub.0161 2405685:6E2WK46K
Keywords: _r:AddedByZotZen

Introducing: A political economy framework for EdTech evidence uptake - Pellini, Arnaldo; Nicolai, Susan; Kreimeia, Adam; Wilson, Sam (EdTech Hub, 2021)
“Without context, words and actions have no meaning at all” – Gregory Bateson Evidence only makes a difference if it is used. While the EdTech field suffers from significant gaps in knowledge, more research won’t mean much unless it can be used to inform policy and decision-making. And to do this, an understanding of the context and of how individuals…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707924 2405685:24RG82ZT
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Additional Funding Available: Call for Research Proposals - EdTech responses to Covid-19 - Kreimeia, Adam (EdTech Hub, 2020)
We are excited to announce that there is now increased funding available for projects through our Call for Research Proposals: EdTech responses to Covid-19, which closes on Friday 27th November 2020. As part of this window, additional funding, up to a total value of £50k, may be available to a small number of applications, particularly where they allow for comparison…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708240 2405685:U3A62288
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
ZenodoArchiveID: 7701270 ZenodoArchiveConcept: 7701269 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7701270 10.53832/edtechhub.0149 2405685:6V4DBZR8
Keywords: _r:AddedByZotZen

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651935 previousDOI: 10.5281/zenodo.4923094 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4923094 10.5281/zenodo.5651935 2339240:6ELB8P84 2339240:HZ3EBZ29 2405685:79JJ5T29 2405685:P8IAN448 2405685:RU8ET9S2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
ZenodoArchiveID: 7691834 ZenodoArchiveConcept: 7691833 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7434218 10.5281/zenodo.7691834 10.53832/edtechhub.0148 2405685:GXM765F3
Keywords: _r:AddedByZotZen

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707872 2405685:9EPB5ZXS
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6981598 ZenodoArchiveConcept: 6981597 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6981598 10.53832/edtechhub.0105 2405685:BDT76583
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

Francophone countries and COVID-19 EdTech response (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. One thing about coronavirus is clear — it does not respect borders. The COVID-19 pandemic has resulted in school closures across the world. With about 300 million French speakers worldwide, here we consider some initial lessons from francophone education systems, their EdTech response, and the importance of cooperation of countries…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707818 2405685:HSFC8I7U 2405685:Z97WAI9K
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Education during the COVID-19 crisis: Opportunities and constraints of using EdTech in low-income countries (EdTech Hub, 2020)
During this time of crisis, education will not be business-as-usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t stop — but they could be helped by the right EdTech tools.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707786 2405685:8JSCGYMM 2405685:P3KEJIPR
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Reviewing the research literature in educational technology for development: Balancing rigour and inclusivity - Jordan, Katy (EdTech Hub, 2019)
shortDOI: 10/ghgnf5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3581041 10/ghgnf5 2405685:YXIGT4W9
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _zenodoETH

Solutions EdTech face au COVID-19 dans les pays francophones (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Une chose est sûre avec le coronavirus – il n’a pas de frontière. Depuis son émergence, le coronavirus a causé la fermeture d’écoles dans le monde entier. Ce nouveau blog post s’intéresse aux près de 300 millions de francophones dans le monde et aux leçons que nous pouvons tirer de…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707820 2405685:SVXJAUKP
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Rapid‌ ‌Evidence‌ ‌Review:‌ ‌Accelerated‌ ‌Learning‌ ‌and‌ ‌EdTech‌ (EdTech Hub, 2020)
Rapid‌ ‌Evidence‌ ‌Review:‌ ‌Accelerated‌ ‌Learning‌ ‌and‌ ‌EdTech‌ Download report (PDF) Key Findings Accelerated learning programmes focus on speeding up learning. They commonly do so by focusing on cognitive development, social and emotional learning, interactive pedagogy and community support. These programmes further commonly use diagnostic needs assessment and flexible approaches to education, to help children to catch up on missed learning.…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707794 2405685:QURIACXM 2405685:U53B2E7E
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10354009 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1002 ZenodoArchiveConcept: 10354008
Keywords: _r:AddedByMyEducationEvidence

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6543151 10.53832/edtechhub.0125 2405685:VNE3Q93U
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707926 2405685:FB4FWFP9
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Iniciativas para el desarrollo de habilidades CTIM de las adolescentes en la región de LAC - Villavicencio, Xuzel; Myers, Christina; Coflan, Caitlin (EdTech Hub, 2022)
El presente documento se elaboró en respuesta a una solicitud de la oficina de UNICEF en Argentina presentada al Servicio de Asistencia de EdTech Hub en noviembre de 2021. El equipo de UNICEF solicitó una lista seleccionada de iniciativas para el desarrollo de habilidades en ciencia, tecnología, ingeniería y matemáticas (CTIM) de las adolescentes de la región de América Latina y el Caribe (LAC). El documento ofrece una introducción al concepto de igualdad de género y antecedentes acerca de la participación de las mujeres en los campos de CTIM en la región de LAC y en Argentina. El documento también ofrece una serie de recomendaciones transversales basadas en las iniciativas analizadas. Palabras clave: STEM; Género;CTIM; LAC; Argentina; tecnología; Ciencias; igualdad de género An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6497816 10.53832/edtechhub.0091 2405685:TR78WPA9
Keywords: F: Helpdesk response; _r:AddedByZotZen

Resilient by Design: Ukraine’s EdTech Response during Wartime - Bhatt, Margi (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15656819 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1122 ZenodoArchiveConcept: 15656818
Keywords: Hide; _comingsoon; _r:AddedByMyEducationEvidence

Helping improve the Kenya Education Cloud with a SWOT analysis - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
In early 2021, EdTech Hub partnered with the Kenya Institute of Curriculum Development to support them to analyse the strengths, weaknesses, opportunities and threats of the Kenya Education Cloud. This blog highlights what we learnt, and lessons that can inform the development of Virtual Learning Environments around the world. Governments all over the world responded to Covid-19 school closures by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707900 2405685:F5HJ29AQ
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Report launch: Education for the most marginalised post-Covid-19 - Unwin, Tim (EdTech Hub, 2020)
With the support of EdTech Hub, members of the UNESCO Chair in ICT4D have worked hard with colleagues across the world over the last six months to craft an innovative and practical report on how governments can learn from their experiences of Covid-19 to create resilient education systems that use digital technologies wisely, effectively and appropriately. We are all very…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708252 2405685:AQD8NUW9
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Reflections on finding French digital education resources - Masrour, Vahid (EdTech Hub, 2020)
Photo credit: SIL Cameroon Read in French In October, EdTech Hub and Learning Equality put out a call to find French educational resources with the aim of making these resources more accessible to Francophone learners not connected to the internet. This post by Vahid Masrour, Learning Equality’s Curriculum Operations Specialist, highlights observations and recommendations from this process. He shares further…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708246 2405685:ZEC7MLXB
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

À propos de notre recherche de ressources pédagogiques numériques en français - Masrour, Vahid (EdTech Hub, 2020)
Photo credit: SIL Cameroon Lire en anglais Durant le mois d’octobre, EdTech Hub et Learning Equality ont lancé un appel afin de trouver des ressources pédagogiques en français, dans le but de les rendre plus accessibles aux apprenants francophones qui ne disposent pas de connexion à internet. Ce post, préparé par Vahid Masrour, Curriculum Operations Specialist pour Learning Equality, présente…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708244 2405685:FQPNCKCL
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Solutions EdTech face au COVID-19 dans les pays francophones - Lwamba, Etienne (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Une chose est sûre avec le coronavirus – il n’a pas de frontière. Depuis son émergence, le coronavirus a causé la fermeture d’écoles dans le monde entier. Ce nouveau blog post s’intéresse aux près de 300 millions de francophones dans le monde et aux leçons […]
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707816 2405685:3V3HQS3W
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6400980 10.53832/edtechhub.0086 10.53832/edtechhub.0088 2405685:29Z2JFJT 2405685:CB5GGAXU
Keywords: _r:AddedByZotZen

EdTech Systems Research (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5827679 2405685:FNP6VRSS
Keywords: _r:AddedByZotZen

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Using innovative methods to train teachers of blind children: what we learned - Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Governments all over the world have closed learning institutions because of the Covid-19 pandemic, including in Kenya. This has exacerbated the global learning crisis and made it more difficult for teachers, parents, and caregivers to include children with disabilities in quality education. To ensure learners with disabilities were not left behind during Covid-19 school closures, eKitabu partnered with EdTech Hub…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707952 2339240:Y7EARNQ6 2405685:HKG7DF93 2405685:WD8FQQ9D
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
ZenodoArchiveID: 4706031 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706031 2339240:LNRXZMBD 2405685:RG93WYZD
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

‘6Ps’ audit tool - Rahman, Asad; Carter, Alice (EdTech Hub, 2022)
EdTech interventions so often fail to take into consideration the broader system they work within. EdTech Hub has created this tool to assess interventions and identify any gaps in the thinking that might stop an intervention from working. Keywords: innovation; education system; 6Ps; tool An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0117 2339240:DP8CCUUK 2405685:2FMS5BBU 2405685:58EFZM9F
Keywords: _r:AddedByZotZen

China: testing a decade of online education preparation - Liangdi, Xu; Groenewegen-Lau, Jeroen (EdTech Hub, 2020)
ZenodoArchiveID: 4705990 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705990 2339240:S2B995E4 2405685:P5B4YWID
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

STEM Skills Initiatives for Adolescent Girls in the LAC Region - Villavicencio, Xuzel; Myers, Christina; Coflan, Caitlin Moss (EdTech Hub, 2022)
This report was produced in response to a request from the UNICEF country office of Argentina and presents a curated list of science, technology, engineering, and mathematics (STEM) skills initiatives for adolescent girls in the Latin American and Caribbean (LAC) region. It also provides an introduction to gender equality and background on the participation of women in STEM fields in the LAC region — as well as cross-cutting recommendations based on an analysis of a series of initiatives. Key words: STEM; Gender; Girls; LAC; Argentina; technology; Science An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6402444 10.53832/edtechhub.0085 2405685:I8GTEI7T 2405685:MFYZUPKU
Keywords: F: Helpdesk response; _r:AddedByZotZen

Financial sustainability of digital learning environments - Oliveira, Andre Correade; Rui, YangTingting; Upadhyay, Arjun (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7847815 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7847815 ZenodoArchiveConcept: 7847814
Keywords: _comingsoon; _r:AddedByZotZen

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Social Emotional Learning and EdTech: Resources, Examples, and Effective Practices - Rui, Yang (Tingting) (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5778309 2405685:8TZZZUMT
Keywords: F: Helpdesk response; _r:AddedByZotZen

Five lessons learnt from Bangladesh's experience responding to COVID-19 - Sarwar, Mohammad Afzal Hossain; Hossain, Iqbal; Kaye, Tom (EdTech Hub, 2020)
by Md. Afzal Hossain Sarwar (a2i), Iqbal Hossain (UNICEF Bangladesh) and Tom Kaye (EdTech Hub) In recent months, the EdTech Hub has produced a range of documents to support and guide countries as they develop and implement plans to help students keep learning during school closures. Some of the work we have produced includes: a guide to a five-part response…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707856 10.5281/zenodo.4707858 2339240:3JLSUFML 2339240:PISQI3AG 2405685:7G3XE8J6 2405685:HXB42AHC 2405685:PH8ICW77 2405685:RDMBW97E
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Mapping EdTech interventions within the Ministry of Education of Ghana. Preliminary Data - Ampofo, Rudolph; Korboe, David; Radford, Kate; Mazari, Haani (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6722859 10.53832/edtechhub.0099 2405685:3VQU7QGJ
Keywords: _r:AddedByZotZen

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

Help us improve education through technology: Sign up for user research (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. This week we kicked off our project to make our website more useful during the coronavirus (COVID-19) pandemic. This is part of the EdTech Hub’s strategy to respond to the pandemic, by providing rapid, actionable information and advice to government decision-makers. We want to help decision-makers navigate the opportunities and challenges of…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707822 2405685:FHYYQFSX
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
ZenodoArchiveID: 4705912 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705912 2339240:26FUGGA3 2339240:X339ME8R 2405685:EHKCNED4 2405685:NIVS5RZF 2405685:TWMVIX77
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Distance learning in the context of COVID-19: the case of Rwanda - Ngabonzima, Ernest; Isimbi, Roberte; Mwali, Marie Merci; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4706016 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706016 2339240:F62THLX3 2339240:V5PQVKX2 2405685:ADNJFTFA 2405685:CMDUS73G 2405685:T2JBHFBC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

O Efeito da COVID-19 na Educação em África e Suas Implicações para a Utilização da Tecnologia Um Inquérito sobre a Experiência e as Opiniões de Educadores e Especialistas em Tecnologia - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749656 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749656 2405685:XSK5P8VC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTech Horizon Scan: Rapid scan on emerging EdTech research during the Covid-19 pandemic. - Ampofo, Rudolph; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking and provide insight into a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This edition of the Hub’s Horizon Scan provides a high-level summary of research, blogs, and think-pieces published between October and December 2021, that provide insights and learnings on the adoption and utilisation of EdTech during the Covid-19 pandemic. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6959924 10.53832/edtechhub.0107 2405685:UWIQTDFF
Keywords: _r:AddedByZotZen

SUMMARY Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
ZenodoArchiveID: 4706074 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706074 2339240:8TCJQBLC 2405685:5DWI862Y 2405685:ZWLE9BLR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

How to re-imagine learning in the wake of Covid-19 (EdTech Hub, 2020)
Last week the EdTech Hub, #NextGenEdu, and Education Development Trust convened experts, policymakers, and implementers to discuss their visions for a reimagined approach to learning in the wake of coronavirus. The invited speakers were: Mohibul Hasan Chowdhury, Deputy Minister of Education, Bangladesh Ministry of Education Jim Ackers, Regional Education Advisor, UNICEF South Asia Regional Office Sonam Wangchuk, Founder, Students’ Educational…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707880 2405685:KDWC5B3N
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Building effective COVID-19 education response plans: Insights from Africa and Asia - Otieno, Jenn Cotter; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2020)
by Jenn Cotter Otieno, Eric Kimenyi and Tom Kaye As countries around the world rapidly respond to the educational challenges posed by the COVID-19 pandemic many countries have begun to leverage technology to provide educational continuity. We at the EdTech Hub are working with many countries to help them design interventions to support learning during this crisis. The first question…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707848 2405685:53CUDS8Y 2405685:FTVF4TKE
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How India responded: distance learning in the time of COVID-19 (EdTech Hub, 2020)
As schools began to close earlier in the year, at the EdTech Hub we started to look at how governments pivoted to distance learning, with a number of country case studies exploring this shift. While the full case studies will be released soon, this blog gives an overview of the first of these into India’s response. The onset of COVID-19…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707852 2405685:54S5XRX6 2405685:6JFEC4RJ
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Think Local: Support for learning during coronavirus (COVID-19) could be found from within communities (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. While technology is a potentially powerful tool in low-resourced contexts, technology use is not always possible or appropriate, as previous Hub blogs have asserted. The following blog emphasises the particular role that communities can play in supporting continued learning opportunities for the billions of children whose education has been disrupted by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707810 2405685:8C79QZUZ 2405685:HM8YRCFL 2405685:Q6J6TH8K
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
DOI 10.53832/edtechhub.0147 ZenodoArchiveID: 7652491 ZenodoArchiveConcept: 7652490 2405685:ECXPS38I KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8363989 10.53832/edtechhub.0174 2405685:ECXPS38I 2405685:MDC3E34G
Keywords: _r:AddedByZotZen

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Our Strategy, Part 2: Deep dive into our approach, focus countries, and theory of change - EdTech Hub (EdTech Hub, 2022)
In Part 2 of our strategy, we go deeper into EdTech Hub’s integrated approach to how we work, where we work, and how that comes together with our topics to inform our theory of change. Verna Lalbeharie, Executive Director The EdTech Hub integrated approach We do research because it is imperative to build deep quantitative and qualitative insight regarding how…
KerkoCite.ItemAlsoKnownAs: 2339240:7DMT34XG 2339240:TFZQRG6B 2405685:8AMLEXFH 2405685:TFAGI64Q

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (EdTech Hub, 2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707931 2405685:E65E8VY5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Engaging with equity: insights from our first sandbox meetup - Rahman, Asad (EdTech Hub, 2020)
Talented, committed innovators are working with EdTech all over the world to make sure children continue learning amidst the school closures caused by Covid-19. At the EdTech Hub, we are lucky to work with six such initiatives in Sandboxes. From experimenting with telephone helplines in Afghanistan to testing Whatsapp in refugee camps in Lebanon, to working with an advocacy campaign…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707465 2339240:Z6JFQX9W 2405685:JHAMLTST 2405685:QUU7IUSY
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4705994 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705994 2339240:FMIXJN4W 2405685:VZ3IMPYX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707814 2405685:5ZVJ2YZ5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749654 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749654 2405685:39XPD5EM 2405685:QZ2FJC4E
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
ZenodoArchiveID: 7421516 ZenodoArchiveConcept: 7421515 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7421516 10.53832/edtechhub.0143 2405685:DE7XUSMJ 2405685:IWFRG7US 2486141:MQHWRFUH
Keywords: _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4
Keywords: _r:AddedByZotZen

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
ZenodoArchiveID: 5596875 ZenodoArchiveConcept: 5596874 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5896640 10.5281/zenodo.6504993 10.53832/edtechhub.0055 2405685:HT8ZGKAB 2405685:QAH4K4D6 2405685:SE5JPCX2
Keywords: HLR3; _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6958056 10.53832/edtechhub.0106 2405685:MFH269TU
Keywords: _r:AddedByZotZen

Our Strategy, Part 1: Empowering decision-makers with evidence to improve learning for all - EdTech Hub (EdTech Hub, 2022)
For the last five months, EdTech Hub has been exploring and refining our strategy for advancing evidence in EdTech for low- and middle-income countries. We invite you to explore our thinking for how we will carry out this mission within our context and in partnership with the global EdTech community. Verna Lalbeharie, Executive Director Acknowledgements Thank you to all of…
KerkoCite.ItemAlsoKnownAs: 2339240:AMV4DLSG 2339240:VADKXL3E 2405685:5ZYSLE8K 2405685:TLLYS3BK

Lessons for effective CPD - Synthesis of a Sandbox Learning Session - Plaut, Daniel (EdTech Hub, 2020)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5123352 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5123352 2405685:JN3CGXFK
Keywords: _EdTechHub_Output; _r:AddedByZotZen

Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023358 ZenodoArchiveConcept: 7023357 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023358 10.53832/edtechhub.0110 2405685:FUBDMTM8
Keywords: _r:AddedByZotZen

Methodologies for mapping Ministry of Education EdTech interventions: Lessons from Ghana - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7006706 ZenodoArchiveConcept: 7006705 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7006706 10.53832/edtechhub.0155 2405685:VIURCMFU
Keywords: _comingsoon; _r:AddedByZotZen

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5576416 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5576416 10.53832/edtechhub.0052 2339240:282R466B 2339240:EQWZQPHA 2405685:2B2RMIDY 2405685:AEQDZV3T 2405685:DX6WMTLN 2405685:NNN9EZ7J
Keywords: _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6621244 10.53832/edtechhub.0098 2405685:GV4MKFZH
Keywords: _r:AddedByZotZen

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4585511 10.5281/zenodo.4728170 2405685:G2SH3FP6 2405685:HLMSBECU 2405685:MKH2ZP2T 2405685:TYXJSKEP
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707910 2405685:7HCBSU4P
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Results – Rapid Scans – The EdTech Hub - EdTech Hub (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4MLKCQH6 2405685:M78IF9TS 4656463:IAPZ4MLA

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10652003 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1013 ZenodoArchiveConcept: 10652002
Keywords: _r:AddedByMyEducationEvidence

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4584801 2339240:F47KL5P7 2339240:VJ2SHXTR 2405685:DJHAECID 2405685:JV4FPSJW
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech Hub Quarterly Report October to December 2020 - EdTech Hub Team (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:5X7TAC2B 2405685:5X7TAC2B;10.5281/zenodo.4354796

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
ZenodoArchiveID: 4705451 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705451 2339240:CMSHWXFV 2339240:QDQHFQXB 2405685:2HFSJ78U 2405685:YEQSJBYT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Designing for Scale: Understanding design principles and learning process for a personalised learning platform in Kenya - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596448 ZenodoArchiveConcept: 5596447 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0053 2405685:27K3U5W4

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596872 ZenodoArchiveConcept: 5596871 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0054 2405685:4N5VUGJG

The Impact of a Tech-Supported, School-Based TCPD Model on Learning Outcomes in Tanzania - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596877 ZenodoArchiveConcept: 5596876 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0056 2405685:PFMSZZ8N

Optimising Messaging to Promote Returns to School in Ghana for Marginalised Learners - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596883 ZenodoArchiveConcept: 5596882 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0058 2405685:DMVKGJWQ

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596885 ZenodoArchiveConcept: 5596884 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0059 2405685:7TUWEUKZ

Cost-Effective Technology Approaches to Improve Education Outcomes for Girls: Learning from 41 Girls’ Education Challenge projects - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596887 ZenodoArchiveConcept: 5596886 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0060 2405685:8ZWX2JI5

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
ZenodoArchiveID: 4762316 previousDOI: 10.5281/zenodo.4050155 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4762316 10.5281/zenodo.3990369 10.5281/zenodo.4050155 10.5281/zenodo.4762316 10/ghgk62 2339240:86AAWUD3 2339240:BMRM6MNQ 2339240:RYU57YK3 2405685:BMDY65UF 2405685:CHX3W9RE 2405685:WGYWI78R
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8370318 ZenodoArchiveConcept: 8370317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8370318 10.53832/edtechhub.0175 2405685:XRGSHEUJ
Keywords: _r:AddedByZotZen

Research - EdTech Hub (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:S7VNMT74 2405685:SGN72ZXM

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
ZenodoArchiveID: 4706059 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706059 2339240:3HJRFVNR 2339240:3VR6UC7F 2339240:9U79NYYD 2339240:NCZSLKX5 2339240:UEWQXHSF 2339240:YFCV9UXA 2339240:YMYNESML 2405685:9NJI87R8 2405685:B54L7JGC 2405685:C6QUC3Z7 2405685:D9SU8CEK 2405685:LK4JMG78 2405685:PW66MNDR 2405685:SLJSKY8J 2405685:VSAZQYD7 2405685:Z3XYMJZN
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

EdTech Hub Strategy: Mitigating the impact of COVID-19 on equitable education access and learning - The EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Z9NRHELL 2405685:ID5A529H

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6337916 10.5281/zenodo.6337918 10.5281/zenodo.6338002 10.5281/zenodo.6338007 10.53832/edtechhub.0083 2339240:AZXVF44M 2339240:GZRZGRN7 2339240:MJPJVVCU 2405685:6QCZIQR2 2405685:D9VW8AI3 2405685:PWU63GQS 2405685:QAXG3NCJ 2405685:RKRPWPX5 2405685:VT5Z6XB6 2405685:YBG8MTTQ 2405685:ZDHGEBKD
Keywords: _r:AddedByZotZen

Why the World Needs a Curriculum Alignment Hub - Chandra, Shivi (Learning Equality, 2020)
ZenodoArchiveID: 5534235 previousDOI: 10.5281/zenodo.4314923 previousDOI: 10.5281/zenodo.4768580 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4314923 10.5281/zenodo.4768580 10.53832/edtechhub.0046 2339240:XFMP94YR 2405685:2RMKAHXF 2405685:TLNPJ4IA 2405685:ZNQYTUVV
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Characteristics of effective teacher education in low- and middle-income countries: an overview (HDR10A) - Haßler, Björn; McBurnie, Chris; Allier-Gagneur, Zoe; Damani, Kalifa (EdTech Hub, 2020)
previousDOI: 10.5281/zenodo.3873458 EdTechHub.Copy: 2129771:2BEHBMUH EdTechHub.Copy: 2129771:2BEHBMUH EdTechHub.Copy: 2129771:C6TREICJ EdTechHub.Copy: 2129771:C6TREICJ EdTechHub.Source: 2405685:HFKVA2IQ EdTechHub.Source: <this> KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873458 10.53832/edtechhub.0006 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
previousDOI: 10.5281/zenodo.3873460 EdTechHub.Copy: 2129771:3AV78BC7 EdTechHub.Copy: 2129771:3AV78BC7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873460 10.53832/edtechhub.0008 2129771:3AV78BC7 2339240:FE5LM4QS 2405685:KXY7Q6VT
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Position paper: EdTech for learners (internal working paper). - Damani, Kalifa; Francis, Gill; McIntyre, Nora; Major, Louis; Hollow, David (EdTech Hub, 2020)
ZenodoArchiveID: 5652078 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652078 2339240:FIEKAQG2 2339240:FZHSJ3WP 2405685:RAGXYQWJ
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Decolonising EdTech: A resource list for tackling coloniality and digital neocolonialism in EdTech - Adam, Taskeen; Sarwar, Moizza Binat; Moustafa, Nariman (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5997769 10.5281/zenodo.5997789 10.5281/zenodo.5997811 2405685:6NMRRZ3B 2405685:E9WKENWB 2405685:P6JH9CGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Guidance Note 3 Digital technologies and girls’ education From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684315 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684315 2339240:4SBZJHY4 2405685:QSPCTJDI
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Considering EdTech in climate emergencies: To what extent and when is it feasible? - Mazari, Haani; Baloch, Imdad; Riley, Matthew; Riley, Imdad Baloch and Matthew, Haani Mazari (EdTech Hub, 2022)
New research from EdTech Hub explores the response to climate emergencies following the Pakistan floods - the worst in recent history - and highlights the importance of utilising existing, most accessible technologies to ensure learning continuity.
KerkoCite.ItemAlsoKnownAs: 2339240:T6IF4WAJ 2405685:NRAVNN8F

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Opinion: Why all research programmes should have a helpdesk - Proctor, Jamie (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13694715 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1055 ZenodoArchiveConcept: 13694714
Keywords: _r:AddedByMyEducationEvidence

Researching with teachers with disabilities in Tanzania: adaptations and observations - Hennessy, Sara (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12752114 ZenodoArchiveConcept: 12752113 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1036 10.53832/edtechhub.1037 2405685:Q75XZHT7
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Three Take-Aways on Climate Resilience for Education Systems in East Africa - Simmons, Hannah; Mbugua, Ciku; Barretto, Johnpaul (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14197579 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1070 ZenodoArchiveConcept: 14197578
Keywords: _r:AddedByMyEducationEvidence

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
previousshortDOI: 10/ghgng5 previousDOI: 10.5281/zenodo.3762228 EdTechHub.Copy: 2129771:QQWNSYJR EdTechHub.Copy: 2129771:QQWNSYJR shortDOI: 10/ghgng5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3762228 10.53832/edtechhub.0022 10/ghgng5 2129771:QQWNSYJR 2339240:45F2G56T 2405685:3MKIMX34 2405685:A3T2DQ4D 2405685:WB97BS9V
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Guidance Note 12 Ensuring rigorous monitoring and evaluation of initiatives using digital technologies in education for the most marginalised From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684341 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684341 2339240:ZKX9NWUD 2405685:DXSF5ZX6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 5 Supporting the effective use of digital technologies for learning by refugees and displaced persons From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684319 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684319 2339240:L97RQZU7 2405685:XUE9KMII
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Building a better Learning Management System for teachers: How Agile methods are being used to support education reform in Tanzania - Simmons, Hannah (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13847110 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1064 ZenodoArchiveConcept: 13847109
Keywords: _r:AddedByMyEducationEvidence

EdTech for Digital Personalised Learning - EdTech Hub (EdTech Hub, 2022)
Evidence on how technology can be used to maximise the effectiveness of personalised learning and teaching at the level of the student.
KerkoCite.ItemAlsoKnownAs: 2339240:ZCFHC5VL 2405685:RDDSSH2L

EdTech and Equity: Position Paper - Zubairi, Asma; Jefferies, Kate; Kreimeia, Adam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5140323 2405685:9KIUKW7T
Keywords: _r:AddedByZotZen

From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14266292 ZenodoArchiveConcept: 14266291 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1080 2405685:WIB4DE6R 2486141:TQ3SZHVM
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

Government-led edtech initiatives to improve learning outcomes in Kenya (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7004972 ZenodoArchiveConcept: 7004971 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7004972 2405685:QH86RGE6
Keywords: _r:AddedByZotZen

EdTech and girls education in low- and middle-income countries: which intervention types have the greatest impact on learning outcomes for girls? - Jordan, Katy; Myers, Christina (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5874080 2405685:9RGDIIHD
Keywords: _r:AddedByZotZen

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SLHSYDRF PreviousDOI: 10.5281/zenodo.3377829 PreviousShortDOI: 10/ghgngc KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3377828 10.5281/zenodo.3377829 10.5281/zenodo.3595482 10/ghgngc 2129771:84AIHEAJ 2129771:Q74CFTXR 2129771:SLHSYDRF 2339240:2DHE9CQC 2339240:BF96YT5K 2339240:FJZA9NPX 2339240:NLMLQD75 2405685:6YT2AIMC 2405685:7S8Z2IUF 2405685:RUSE8WYV
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

HDR - Haßler, Björn; Taruza, Takudzwa Charisse; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15485110 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1119 ZenodoArchiveConcept: 15485109
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Cross Cutting Themes - Swindell, Andrew (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15270303 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1111 ZenodoArchiveConcept: 15270302
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Titre du rapport - Traore, Moussa (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10935897 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1021 ZenodoArchiveConcept: 10935896
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Districts of Excellence Toolkit - Burgess, Flic; Beoku-Betts, Iman (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14832497 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1095 ZenodoArchiveConcept: 14832496
Keywords: Hide; _comingsoon; _r:AddedByMyEducationEvidence

Districts of Teaching Excellence Sierra Leone - Beoku-Betts, Iman; Burgess, Flic (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14794031 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1090 ZenodoArchiveConcept: 14794030
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Algorithmic design in EdTech: Investigating adaptivity for learners and teachers in a digital personalised learning tool in Kenya - Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Sun, Chen (EdTechHub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15805704 ZenodoArchiveConcept: 15805703 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1127 2405685:WVDDN399
Keywords: _r:AddedByMyEducationEvidence

Brief 3 - Which design features enable successful DPL - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825860 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1093 ZenodoArchiveConcept: 14825859
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech’s three promising approaches to #SaveOurFuture - Nicolai, Susan; Haßler, Björn (EdTech Hub, 2020)
By Susan Nicolai and Björn Haßler Covid-19 has led to the biggest upheaval to daily life that many of us have ever seen, including for education. Even before schools shut in early March, there was a recognised global learning crisis and some 260 million not in school. The pandemic has further interrupted education for 90% of children around the world,…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707486 2129771:HQIS6BEE 2405685:G5RWH5HE 2405685:PIYPR6M6
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen

The use of Interactive White Boards to support refugee learners - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15692961 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1123 ZenodoArchiveConcept: 15692960
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

A systems analysis of teacher deployment - Frazer, Madleen Madina; Adam, Taskeen; Godwin, Katie; Cameron, Emma; Mackintosh, Alasdair; Koutecký, Tomáš (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368298 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1116 ZenodoArchiveConcept: 15368297
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Low-cost educational messaging in West Africa: evidence on cost-effectiveness - Mitchell, Joel; Mukankusi, Aimée; D'Rozario, Jonny (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12519241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1033 ZenodoArchiveConcept: 12519240
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Guidance Note 14 Partnerships with the private sector and civil society From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684345 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684345 2339240:ZD696VRL 2405685:EGYJSMZC 2405685:UW2H22R7
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Transforming Teacher Deployment: Lessons from a matching algorithm tool - Frazer, Madleen Madina; Adam, Taskeen; Godwin, Katie; Mackintosh, Alisdair; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368169 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1114 ZenodoArchiveConcept: 15368168
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

AI Observatory Webinar Report: unlocking learning outcomes in the age of AI - Luz, Gita (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15149258 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1109 ZenodoArchiveConcept: 15149257
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 1 - How DPL can support FLN and equitable learning in Kenya - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825837 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1091 ZenodoArchiveConcept: 14825836
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 4 - How data from DPL tools can be utilised to support learning - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825872 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1094 ZenodoArchiveConcept: 14825871
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Technology-enabled interventions for psychosocial support and social and emotional learning in education in emergencies - Moustafa, Nariman; Mtungwa, Nothando (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15806037 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1128 ZenodoArchiveConcept: 15806036
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Gender and disability-related influences on teachers’ access to technology-mediated professional learning in Tanzania - Hennessy, Sara; Chachage, Kristeen; Swai, Calvin; Koomar, Saalim; Singal, Nidhi; Massam, Winston; Paskali, Jonathan H.; Adam, Taskeen (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15591957 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1121 ZenodoArchiveConcept: 15591956
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Taskeen Adam; Adam, Taskeen; Mwakabungu, Fika; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14901418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1096 ZenodoArchiveConcept: 14901417
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Exploring the reach and influence of the Southeast Asia Primary Learning Metrics (SEA-PLM) Programme: A Scoping Study - Brugha, Meaghan; Afzal, Nimra; Flam, Rebekka (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13829279 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1063 ZenodoArchiveConcept: 13829278
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Artificial Intelligence and Education Systems in 2035: 14 trends and 5 scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Education in Conflict & Crisis in 2035: 12 trends and 5 scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792765 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1126 ZenodoArchiveConcept: 15792764
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 2 - Overview of the implementation of the tool and the support teachers require to implement DPL - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825850 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1092 ZenodoArchiveConcept: 14825849
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Scaling Online Teacher Professional Development in Bangladesh: Bangladeshi teachers’ experiences of the online training for the National Curriculum Revision - Afzal, Nimra; Atuly, Afsana Sadiq; Mazari, Haani; Clark-Wilson, Alison (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15005589 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1102 ZenodoArchiveConcept: 15005588
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

AI Observatory Webinar Presentation: 7 headlines we have learned about unlocking learning outcomes in the age of AI - Luz, Gita (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15149320 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1110 ZenodoArchiveConcept: 15149319
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapid Evidence Review: Girls' Education and EdTech (EdTech Hub, 2020)
Full PDF Download Key Findings Access to technology has shown to be often disproportionately more empowering for girls relative to boys, with wider benefits which expand beyond formal education. Most studies suggest there is a significant existing gender digital divide: cultural bias and gendered assumptions about girls’ competence and enjoyment of technology, and the benefits […]
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707796 2405685:WS22AEWL
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Strengthening the use of data for decisions on teacher deployment in Sierra Leone: A Geospatial Approach to Workforce Allocation - McBurnie, Chris; Frazer, Madleen Madina; Dube, Gugulethu; Godwin, Katie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14608646 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1082 ZenodoArchiveConcept: 14608645
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Activating local study-groups for children’s learning—an equitable EdTech response? - Power, Tom (EdTech Hub, 2020)
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707840 2339240:SR6Q67QK 2405685:5ETXZ323 2405685:8RXKC68I 2405685:Q539CZ7X
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Assessing the scale-up of a technology-supported, government-led teacher professional development programme in Tanzania: Considering issues of equity, agency, and adaptation, Round 2 Policy Brief - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Hegwa Paskali, Jonathan; Massam, Winston; Mtenzi, Fredrick; Komba, Anneth; Jacob Mrpoe, Winfrida; Anthony, Gervace; Malibiche, Mustapha; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15388175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1118 ZenodoArchiveConcept: 15388174
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Data-Driven Teacher Deployment in Sierra Leone: Practicalities and quantitative analysis of using a matching algorithm in the 2024/25 deployment cycle - Koutecký, Tomáš; Mackintosh, Alasdair; Huti, M; Adam, Taskeen; Godwin, Katie; Frazer, Madleen Madina (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368231 ZenodoArchiveConcept: 15368230 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1115 2405685:ICRSXHTV 2405685:MUWUTSZS 2486141:MRAYINR3
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Usawa na Maamuzi katika Mafunzo Endelevu ya Walimu Kazini yanayowezeshwa na Teknolojia nchini Tanzania: Zana za utafiti - Swai, Calvin; Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Massam, Winston; Mwakabungu, Fika; Paskal, Jonathan; Mutura, Emmanuel; Anthony, Gervace; Mrosso, Vicky; Jacob, Winnie; Komba, Philbert (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14901456 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1097 ZenodoArchiveConcept: 14901455
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
ZenodoArchiveID: 10529049 KerkoCite.ItemAlsoKnownAs: 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 2129771:JC66TBWQ 10.53832/edtechhub.1003 ZenodoArchiveConcept: 10529048
Keywords: _r:AddedByMyEducationEvidence

Collaboration to Realise Kenya’s National Learning Goals through EdTech - Otieno, Jennifer; Omuthe, Ronald; Ampofo, Rudolph (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 10340063 ZenodoArchiveConcept: 10340062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10340063 10.53832/edtechhub.0179 2405685:A76IFCAT
Keywords: _r:AddedByZotZen

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
ZenodoArchiveID: 4486906 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4486906 2339240:NTGE2FPC 2405685:DU497D8A 2405685:HCV5X9YJ
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Our new partnerships with eKitabu, Rising Academies, and Learning Equality (EdTech Hub, 2020)
We are thrilled to announce our new partnerships with three amazing organizations – eKitabu, Rising Academies, and Learning Equality. We’ll be working alongside them in the months ahead to advance equitable educational solutions for the most marginalized learners. We’re excited to offer the Hub as a platform for amplifying their work – making new connections and fostering collaboration across thinkers…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707882 2405685:4DSHAABL 2405685:UXH56ELI
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Supporting innovation in the time of COVID: What we've done and what we'll do next (EdTech Hub, 2020)
When COVID-19 emerged as a clear and present danger, we in the Hub innovation team were forced to rethink our plans for 2020. We previously told you about our work and how it looks to support and scale innovation with real people in real life. Now we had to reassess what this would look like and how it could be…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707842 2405685:INIYKGVN
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15039164 ZenodoArchiveConcept: 15039163 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1103 2405685:IRFH43RX 2405685:SFNCI64Z 2486141:C9Q4ZDTR
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Publish, learn, improve (EdTech Hub, 2020)
This week we’ve designed and prototyped a tool to make our website more useful during the coronavirus (COVID-19) pandemic. We want to enable decision-makers to make informed choices about if, when and how to use EdTech during this crisis. We’re building something to help you find education responses by governments and EdTech tools that support these responses. Given the urgency…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707831 2405685:K2X97KWP 2405685:Y8M4EAQR
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Five things to think about for out-of-school learning during the coronavirus (COVID-19) outbreak (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Today, over a billion learners are affected by closures due to coronavirus (COVID-19). In these unprecedented times we’re committed to playing our role in supporting countries to provide continued education for all learners. Over the coming weeks and months, we’ll be sharing insights and resources about how educational technology (EdTech)…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707798 2405685:GGVB5UAV
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Leveraging Existing Technology in Low-Resource Settings: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

EdTech in Zimbabwe: A Rapid Scan - Dzinotyiweyi, Monica; Taddese, Abeba (EdTech Hub, 2020)
ZenodoArchiveID: 5652131 previousshortDOI: 10/ghgnd5 previousDOI: 10.5281/zenodo.3903838 shortDOI: 10/ghgnd5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3903838 10.53832/edtechhub.0040 10/ghgnd5 2339240:L6LPKDJD 2405685:G4UUX5P3
Keywords: C:Zimbabwe; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

How can governments, schools and teachers support education continuity and good pedagogy under coronavirus (Covid-19)? (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Anna Riggall (Head of Research) and Tony McAleavy (Research Director), Education Development Trust As the horror of Covid-19 became apparent, governments around the world closed schools in their attempts to control the spread of the virus. According to UNESCO, schools are closed in 191 countries, impacting 90% of the world’s…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707824 2405685:6L94W7UK 2405685:H9V63A7B
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The potential of using technology to support personalised learning in low- and middle-income countries - Major, Louis; Francis, Gill (EdTech Hub, 2020)
With schools around the world closed to prevent the spread of COVID-19, we have been undertaking a series of ‘rapid evidence reviews’ to help education decision-makers respond effectively. These reviews aim to provide evidence-based summaries on specific areas of EdTech. In this post, we look at the role of technology in supporting personalised…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707874 2405685:DNNA97P4
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Covid-19, EdTech, and Survey Alignment in Education - Fitzpatrick, Rachael; McIntyre, Nora; Wilson, Samuel; Rose, Pauline (EdTech Hub, 2020)
ZenodoArchiveID: 4768598 previousDOI: 10.5281/zenodo.4314945 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4314945 10.5281/zenodo.4768598 2339240:6DKWXNLP 2405685:84NR98PF
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Guidance Note 2 Sharing Open Educational Resources (OER) with Creative Commons (CC) open licenses From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684309 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684309 2339240:25SFNRMI 2405685:AFN6CFAX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 6 Digital technologies and education in Small Island Developing States (SIDS) From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684323 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684323 2339240:UJ59J7KR 2405685:MGNGURSV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech Interventions for Deaf Learners in Pakistan: Sprint 1 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2020)
ZenodoArchiveID: 5652083 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652083 10.53832/edtechhub.0130 2339240:HBZUCV8U 2405685:CYESNSWU
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf

Guidance Note 10 Prioritising effective and appropriate teacher training From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 5652081 previousDOI: 10.5281/zenodo.4706041 previousZenodoArchiveID: 4706041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684335 10.5281/zenodo.4706041 10.5281/zenodo.5652081 2339240:FX4YE46B 2339240:GHL6MEA3 2339240:LB4BCD79 2405685:7E62A3FM 2405685:JBRS94SA 2405685:UKL5P7WM 2534378:35MTF3B9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707480 2405685:29RAGPFX 2405685:E2UQW73U
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Guidance Note 9 Involving marginalised young people in the design of their own education From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684331 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684331 2339240:NKWXU7PD 2405685:NN3UCNCQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Mapping National Digital Learning Platforms: Full Dataset - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Hasiniavo, Rasolohery (EdTech Hub, 2023)
The dataset provided here as a link to a spreadsheet presents raw data from a global mapping exercise of 471 national digital platforms across 184 countries conducted by EdTech Hub as part of a Helpdesk request from UNICEF. The mapping exercise examined three key areas of availability, usability, and inclusivity of national digital learning platforms. Analysis from the dataset was used to generate a report on national digital learning platforms. The datasheet includes the authors’ organisation of the dataset under key indicators. Readers can use the datasheet to replicate or conduct their own analysis. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 10256767 ZenodoArchiveConcept: 10256766 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10256767 10.53832/edtechhub.0178 2405685:SPWJF5UR
Keywords: _r:AddedByZotZen

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684327 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684327 2339240:J6VCPUDV 2405685:57FXZ5EA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 1 In the local context — using digital technologies to develop local content From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684307 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684307 2339240:WETE6Y2I 2405685:WWC3MTHS
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 4 Inclusion and accessible learning for people with disabilities From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684317 2339240:LKN74WQK 2405685:56QA2K9Y
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13907321 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1067 ZenodoArchiveConcept: 13907320
Keywords: _r:AddedByMyEducationEvidence

Guidance Note 7 Ensuring resilient connectivity From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684325 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684325 2339240:KRAUGIY3 2405685:3KMQRBG7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 11 Using digital technologies effectively in support of learning and training for employment From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684337 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684337 2339240:G35WT8JB 2405685:G8GC8P3G
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 13 Ensuring that children are safe when using digital technologies for learning From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684343 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684343 2339240:F7A5DUAY 2405685:JI5QK62G
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note Annex 4 From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684351 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684351 2339240:A5EM5HJ4 2405685:39NC6LPG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Raising readers: Kenya schools use of technology to improve parent and carers' engagement in literacy learning: Inception Report - Nicolai, Susan; Zubairi, Asma; Bapna, Akanksha; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5784255 2405685:ZT3TGJ26
Keywords: _r:AddedByZotZen

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
10.5281/zenodo.4913283 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0048 10.53832/edtechhub.0049 2339240:487NSL2N 2339240:96WXZFG3 2339240:BXUFCQ98 2339240:QUJFSUDE 2405685:4NFT3P7H 2405685:MZSKKWUZ 2405685:NVIUXYC6 2405685:PIXT9J66 2405685:RL5CTZU3 2405685:U8GMZZ48 2486141:7MQA6V3G 4656463:6378IJC5 4656463:TD3MYCHJ
Keywords: _EdTechHub_Output; _MELA_seen

Using evidence in practice when there is high uncertainty on what works - Rahman, Asad; Simpson, Lea; Wilkinson, James; Kuria, Catherine; Kably, Nathan; Plaut, Daniel; Tanweer, Rabia; Mbugua, Ciku (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7645994 ZenodoArchiveConcept: 7645993 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7645994 10.53832/edtechhub.0158 2405685:8VUZEK29
Keywords: _r:AddedByZotZen

Case study: Building strong institutional capacity and expertise in data for decision-making through developing a unified data management system. - Ampofo, Rudolph; Simiyu, Genevieve; Ayinga, Ussif (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10617486 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1009 ZenodoArchiveConcept: 10617485
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
ZenodoArchiveID: 10079721 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1000 ZenodoArchiveConcept: 10079720
Keywords: _internal; _r:AddedByMyEducationEvidence

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - EdTech Hub (2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
KerkoCite.ItemAlsoKnownAs: 2405685:EVU4DEWP 4042040:T3S2AEMN

Research publication strategy and proposed publications - Haßler, Björn; McIntyre, Nora; Hollow, David; Jordan, Katy; Hennessy, Sara; Brugha, Meaghan; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SNH4JG9L EdTechHub.Source: 2339240:94ZP3EK4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3624978 2129771:SNH4JG9L 2339240:94ZP3EK4 2339240:VMNDUZSF 2405685:2GLWRD86
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Learning through television in low-income contexts: mitigating the impact of coronavirus (COVID-19) - Watson, Joe (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Joe Watson, research assistant at the University of Cambridge One of the many consequences of COVID-19 is that more than a billion caregivers will soon face the stark (and often scary) realisation that they must become their children’s teachers. This will be particularly difficult in low-income contexts where…
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707800 2339240:ELSHST8I 2339240:NH74Q4D5 2339240:SEDLSMKA 2339240:SRTNHXEM 2339240:ZL8JVQGI 2405685:54S7693K 2405685:BGP7GCNU 2405685:DLE5F2DK 2405685:FF93KYQR 2405685:LA5D6QFR 2405685:PCDTZ7S3 2405685:PD7SX3IX 2405685:SS7E2HN4 2405685:VCLDWRIS 4803016:U4W8F4AZ BGP7GCNU SEDLSMKA
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15077892 ZenodoArchiveConcept: 15077891 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1104 10.53832/edtechhub.1105 10.53832/edtechhub.1107 10.53832/edtechhub.1108 2405685:FR4GREKJ 2405685:XG7G3FDM
Keywords: _r:AddedByMyEducationEvidence

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken, Rachel Chuang (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.
KerkoCite.ItemAlsoKnownAs: 2339240:G82EPYXB 2405685:MKLN5KM6

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken, Rachel Chuang (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.
KerkoCite.ItemAlsoKnownAs: 2339240:G82EPYXB 2405685:MKLN5KM6

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652942 10.53832/edtechhub.0068 2339240:GXUF5TA5 2339240:HHY6M835 2339240:SUEMN855 2405685:8S3IIB2B 2405685:EE9QCGHI 2405685:Q7YZW4YW 2405685:RN79UTQY 4656463:GIIQKETU 4656463:Y8LQGZWY
Keywords: _r:AddedByZotZen

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen

A scoping review of technology in education in LMICs - descriptive statistics and sample search results - Haßler, Björn; McIntyre, Nora; Mitchell, Joel; Martin, Kevin; Nourie, Kristi; Damani, Kalifa; Kristi Nourie; Kalifa Damani (EdTech Hub, 2020)
EdTechHub.Copy: 2129771:GYTVIZJV EdTechHub.Copy: 2129771:MBZLFNDM EdTechHub.ThisIsNot: 2339240:2387P995 2339240:8RA9UD7W shortDOI: 10/ghgk6h KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631588 10/ghgk6h 2129771:56GZ7UBP 2129771:9VXUZISD 2129771:ADGISTZU 2129771:GYTVIZJV 2129771:MBZLFNDM 2339240:2387P995 2339240:65KP6SVQ 2339240:6FUA4SDV 2339240:85SBE7SC 2339240:8RA9UD7W 2339240:IXIRDBKK 2339240:STPRNPV3 2405685:BBQI3VSA 2405685:CMRISZHV 2405685:F6UAIKKN 2405685:QJTH2UXC 2405685:R88UVQZ7 503888:7EH7BANW 503888:PI9FLM7C
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:v; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Technology in education in low-income countries: Problem analysis and focus of the Hub's work - Hennessy, Sara; Jordan, Katy; Hassler, Bjoern; Hollow, David; Brugha, Meghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2339240:EYQWGP5R 2405685:ZGFQHAS3

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
ZenodoArchiveID: 5652005 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652005 2405685:RT5H8XNG
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7510031 ZenodoArchiveConcept: 7510030 KerkoCite.ItemAlsoKnownAs: 2129771:K9HHIYYP 10.5281/zenodo.7510031 10.53832/edtechhub.0156 2405685:B8SQMMBA
Keywords: _r:AddedByZotZen

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6497554 2339240:S7M2CQ4J 2405685:BRY3EXFT 2405685:KAZQRPA7
Keywords: _r:AddedByZotZen

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707838 2405685:84ZQF884
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7966434 ZenodoArchiveConcept: 7966433 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7966434 10.53832/edtechhub.0168 2405685:CQ8JNCH8
Keywords: _r:AddedByZotZen

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
ZenodoArchiveID: 5652036 Dates: 13-11-2020 — Actualizado el 09-01-2021 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652036 10.6018/red.453621 2405685:2BIQKP9C 2405685:IVHRNTQ7 2405685:L7Y5JD68 2405685:ZXQZ3FVV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

EdTech Interventions Database - EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3P7HKD8E 2405685:38GA4ZAF

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
ZenodoArchiveID: 5652007 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652007 2405685:KZ6FTNMC
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Guidance on Facilitation of E-Learning - Dzinotyiweyi, Monica; Chuang, Rachel; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396251 10.53832/edtechhub.0087 2405685:CMEQA5F7
Keywords: F: Helpdesk response; _r:AddedByZotZen

The global stakes of digitalization in education - Haßler, Björn (2021)
PreviousDOI: 10.5281/zenodo.4888604 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4888887 2405685:J49DGN5M
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

What Matters Most for Teacher Deployment? A case study of teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman; Bernard-Jones, Lydia; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6530321 10.53832/edtechhub.0095 2129771:G2ULWZXN 2339240:5JUXJ5N6 2339240:F43SL362 2405685:8GN4RWMR 2405685:L4RY53KI 2405685:Q8366KLT 2405685:XNBZSCS7 2486141:Z5CMZLCE
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Sandbox Lean Cost Model - Rahman, Asad (EdTech Hub, 2020)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5147557 2405685:C44MFZNK
Keywords: _r:AddedByZotZen

Sandbox Meet-up Planning Template - Rahman, Asad (EdTech Hub, 2020)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5147564 2405685:JXX8J5WJ
Keywords: _r:AddedByZotZen

LGA Implementation Guide for Teacher Continuous Professional Development - Tanzania Institute of Education; Ministry of Education, Science & Technology; President’s Office — Regional and Local Governance (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5202057 2405685:U7NR3KP4
Keywords: _r:AddedByZotZen

test - jac, nyili (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524863 2405685:86XEZU2S
Keywords: _r:AddedByZotZen

Guidebook to Successful Implementation of Digital Education - Traore, Moussa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5719833 2405685:RTJ2Z8MX
Keywords: _r:AddedByZotZen

School Infrastructure Survey - Adam, Taskeen; Koomar, Saalim; Hennessy, Sara (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5866554 2405685:VIFG4IFF
Keywords: _comingsoon; _r:AddedByZotZen

Technology Options for TCPD in Tanzania - Haßler, Björn; Mtebe, Joel; Abdelrahman, Salma; Kondor, Oscar; Mashauri, Aron; Adam, Taskeen; Koomar, Saalim (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5874600 2405685:X8QRZ5EJ
Keywords: _r:AddedByZotZen

Libya’s Roadmap for Distance Learning (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5901508 2405685:2WMNXSHF
Keywords: F: Helpdesk response; _r:AddedByZotZen

Report on research outcomes - McBurnie, Chris; Godwin, Katy; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6320778 10.53832/edtechhub.0082 2405685:KT9PMHDT
Keywords: _r:AddedByZotZen

Engagement Strategy For UNICEF Pakistan (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6379314 2405685:AIRHC5TB
Keywords: _r:AddedByZotZen

Reference collection - Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6615096 2405685:TZMR2EZU
Keywords: _r:AddedByZotZen

Education in Sub-Saharan Africa - John, Doe; Jane, Doe (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6798426 2405685:ZM55V7KM
Keywords: _r:AddedByZotZen

Systems, applications and technologies for e-learning - Traore, Moussa (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6811445 2405685:B6QXU3J3
Keywords: _r:AddedByZotZen

Technology and School Mapping - Vijil, Alejandra; Godwin, Katie; Mackintosh, Alasdair; Ramirez, Ana (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6974072 ZenodoArchiveConcept: 6974071 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6974072 2405685:IJ2GD927
Keywords: _r:AddedByZotZen

The National Numeracy Programme — Outputs Register - Haßler, Björn (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7581622 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7581622 ZenodoArchiveConcept: 7581621
Keywords: _r:AddedByZotZen

Education Sector Contingency Plan: Guidelines and Templates - Vijil-Morin, Alejandra; Villavicencio, Xuzel; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7590218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7590218 ZenodoArchiveConcept: 7590217
Keywords: _r:AddedByZotZen

Model Safe Education Plan - Vijil-Morin, Alejandra; Villavicencio, Xuzel; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7593861 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7593861 ZenodoArchiveConcept: 7593860
Keywords: _r:AddedByZotZen

Monitoring and Evaluation Framework - Vijil-Morin, Alejandra; Villavicencio, Xuzel; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7593881 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7593881 ZenodoArchiveConcept: 7593880
Keywords: _r:AddedByZotZen

Sustainable Solutions to Rural Girls’ Education: A Rapid Evaluation of Lyra in Tanzania - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7642746 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7642746 ZenodoArchiveConcept: 7642745
Keywords: _r:AddedByZotZen

Learners and Caregivers' Barriers and Attitudes to SMS-based Mobile Learning in Kenya: Key findings from a telephone survey - Jordan, Katy; Damani, Kalifa; Myers, Christina; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7689021 ZenodoArchiveConcept: 7689020 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7689021 10.53832/edtechhub.0162 2405685:FQV2DUEH 2405685:JV87UGDX
Keywords: _r:AddedByZotZen

Livrable 5: Guide pratique pour les enseignants: comment utiliser la plateforme numérique? - Messa, Angele; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8058585 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8058585 ZenodoArchiveConcept: 8058584
Keywords: _r:AddedByZotZen

Bringing Digital Learning to Rural Schools: A Rapid Evaluation of Lyra in Africa - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8391601 ZenodoArchiveConcept: 8391600 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7857255 10.5281/zenodo.8391601
Keywords: _r:AddedByZotZen

EGates Knowledge Pack - Moustafa, Nariman (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10619937 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1010 ZenodoArchiveConcept: 10619936
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6339212 10.53832/edtechhub.0096 2339240:VJZWBP65 2405685:6JLQ7UC6 2405685:KQUDWCXC
Keywords: _r:AddedByZotZen

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Consultants needed for UNESCO ACCRA's review of ICT in Education Policy in Ghana - Tahi (EdTech Hub, 2021)
ICT Transforming Education in Africa: Review of ICT in Education Policy in Ghana TERMS OF REFERENCE (TOR) FOR INDIVIDUAL CONSULTANTS 1. Background/Context UNESCO Korean Funds-In-Trust ICT Transforming Education in Africa is a project developed under the UNESCO-Korea Funds-in-Trust framework to support a selected number of Sub-Saharan African countries to test scalable and effective models of using information and communication technologies…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707948 2405685:P2RAXUE3
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Implementing a virtual learning environment in a resource-constrained setting: five key reflections - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
Implementing a virtual learning environment is a challenge in any situation. But how do you implement one in a country with few resources, lacking technological infrastructure, and no experience with virtual learning? In response to Covid-19, Zanzibar is planning to implement a virtual learning environment (VLE) to complement its print-, radio-, and TV-based distance education programmes. In Zanzibar, an autonomous…
PreviousDOI: 10.5281/zenodo.4707995 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708006 2405685:K899A8PP 2405685:WZPDTZHA
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

New Brief: Monitoring Distance Learning During the Covid-19 Pandemic - Bashir, Amreen; Groeneveld, Caspar; Kaye, Tom (EdTech Hub, 2020)
In the initial rush to respond to school closures, countries focused on rolling out distance education. Policy-makers now realise that effective distance education requires robust data generated via high-quality monitoring. This blog highlights the findings of a brief synthesising effective practices in monitoring distance education. Since March 2020, the Covid-19 pandemic has impacted 36 million learners in Bangladesh. Schools closed…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708238 2405685:73G8TGWV
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How Bangladesh repurposed pre-existing online platforms to reimagine education during Covid-19 - Bangladesh), Anir Choudhury (a2i (EdTech Hub, 2021)
Forty-two million. That is the total number of students in Bangladesh. Forty-two million potential leaders of tomorrow. Forty-two million reasons to be hopeful for the country’s future. Forty-two million students who, because of Covid-19, were left without classrooms, without their friends, without their schools and colleges – without formal education.
KerkoCite.ItemAlsoKnownAs: 2405685:HVNU4INN 2405685:TA8WC382
Keywords: _EdTechHub_Output

Effective Assessment and Progress Monitoring in an Online Environment: A Study in Six Countries - T4 Education; EdTech Hub (EdTech Hub, 2022)
The study was undertaken in six countries – Bangladesh, India, Nigeria, Pakistan, Philippines, and South Africa. The data collection involved focus group discussions with two held in each country..
KerkoCite.ItemAlsoKnownAs: 2339240:PA9TD6UB 2405685:E66UZCLZ

الامتحانات عبر الإنترنت في سياقات الطوارئ: هل المراقبة، والتقنيات الأخرى، مجدية في سوريا لتيسير عقد امتحانات تشمل جميع الطلاب؟ - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; AlMekdad, Bayan; Sabboura, Rani; Sheqem, Yazeed (EdTech Hub, 2022)
كلمات مفتاحية: الامتحانات عبر الإنترنت، تكنولوجيا مراقبة الامتحانات، سياقات الطوارئ، سوريا خلاصة: الغرض من هذه الوثيقة تقديم دليل يمكن استخدامه من قبل الممارسين في مجال التعليم العاملين في سياقات الطوارئ لتقييم مدى جدوى تنفيذ الامتحانات الإلكترونية واستخدام تكنولوجيا مراقبة الامتحانات. سيتطلب عقد الامتحانات عالية المخاطر عبر الإنترنت في سوريا وفي سياقات طوارئ أخرى استثمارات كبيرة لتحقيق المتطلبات الأساسية اللازمة للجدوى والمصداقية. تشمل هذه المتطلبات الأساسية الكهرباء والإنترنت والأجهزة، بالإضافة إلى تطوير المهارات الرقمية اللازمة للطلاب لتقديم الامتحانات عبر الإنترنت وللمعلمين والإداريين لتيسير الامتحانات عبر الإنترنت. ينبغي بذل المزيد من الجهود لمنع تسريب المعلومات حول الأسئلة ومحتوى الامتحانات، ولتشجيع التغيير الثقافي حول الامتحانات عبر الإنترنت. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7143871 ZenodoArchiveConcept: 7143870 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7143871 10.53832/edtechhub.0124 2405685:9DZXFIC7
Keywords: _r:AddedByZotZen

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10616734 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1008 ZenodoArchiveConcept: 10616733
Keywords: _r:AddedByMyEducationEvidence

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10628960 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1011 ZenodoArchiveConcept: 10628959
Keywords: _r:AddedByMyEducationEvidence

Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
ZenodoArchiveID: 5652080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652080 2339240:VJNSF4EV 2339240:Z6ZIBS2B 2405685:6E2K4GGE
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (2020)
Presentation given at BE2, 2020-10-06.
shortDOI: 10/ghgnf4 KerkoCite.ItemAlsoKnownAs: 10/ghgnf4 2129771:WPJL8SN3 2339240:7TXCEBE6 2405685:5VQMVDB9
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Save our future - Haßler, Björn; Sagun, Rose (2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749380 2405685:QLTPHU6B
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodoODE

#FindFrench: a collaborative search for educational resources in French (EdTech Hub, 2020)
And we need your help! Learning Equality’s Curriculum Operations Specialist, Vahid Masrour, shares more. If you’re teaching or learning during Covid-19 school closures, you’ve probably encountered many solutions proposed for virtual learning environments relying on digital resources. All over the world, people are turning to digital resources — textbooks, lesson plans, videos, tutorials, learning applications, and libraries — to keep…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707893 2405685:YMNW6GG3 2405685:YWNXT2VZ
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Africa’s Covid-19 opportunity (EdTech Hub, 2020)
Educators in Africa are optimistic about the opportunities that Covid-19 brings for reform and innovation in education. That’s the headline from a survey eLearning Africa recently conducted, in which 1,600 education and technology professionals from 52 countries in Africa were asked for their thoughts on the longer-term effects of the pandemic. Despite what it’s doing to societies and economies around…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707890 2405685:AESZ5WMM 2405685:YER28PCY
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

What we have learnt from designing and implementing tablet-based learning across the world (EdTech Hub, 2020)
Written by Susan Colby (Imagine Worldwide) and Nicola Pitchford (University of Nottingham) As COVID-19 has disrupted education worldwide, more organizations and governments are exploring using tablet-based learning models to provide children with flexible access to learning that can take place anywhere. When implemented well, tablet-based learning can empower learners to build skills and knowledge through the use of technology. Children…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707870 2405685:YJ2GWVMA
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Leaving no one behind: technology and the education sector response to COVID-19 in Rwanda (EdTech Hub, 2020)
By Ernest Ngabonzima, Roberte Isimbi, Marie Merci Mwali, Arnaldo Pellini A swift policy response When COVID-19 reached Rwanda, the Ministry of Education (MINEDUC) was quick to shut schools and make use of technology to support and enable distance learning. This includes e-learning platforms and the use of private and public media channels. The first teaching radio programmes were introduced just…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707854 2405685:PBVEZH79
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

What are countries doing that already use remote learning extensively? What can we learn from them? - Gould, Briony (EdTech Hub, 2020)
What are countries doing that already use remote learning extensively? What can we learn from them? Full Report PDF Download Summary of report What’s on this page Summary of report Scope of study Key themes Scope of study This report provides a rapid evidence summary of the history, evolution, coverage, impact (successes and challenges) of remote learning in four countries…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707772 2405685:34IM2QJE 2405685:Y2TV9NH8
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Overview of emerging country-level response to providing educational continuity under COVID-19: Best practice in pedagogy for remote teaching - Gould, Briony (EdTech Hub, 2020)
Overview of emerging country-level response to providing educational continuity under COVID-19: Best practice in pedagogy for remote teaching Full Report PDF Download Scope of Report This report provides a rapid evidence summary of what is known about best practice in teaching when school students are educated by distance learning. It considers both theoretical concepts and empirical evidence relating to the…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707768 2405685:37SUUB79 2405685:GWN8BWPM 2405685:K5NP3ZNE 2405685:L2HPYEFI
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Gould, Briony (EdTech Hub, 2020)
What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? Full Report PDF Download Summary of report What’s on this page Summary of report Scope of study Summary of findings China’s response to Covid-19 built on the distinctive foundations of its existing education political economy, in particular China appears…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707776 2405685:GXS53XYJ 2405685:NAH5BIE5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Curriculum Reform & Building Back Better. - Chuang, Rachel; Mullan, Joel (2020)
This EdTech Hub Helpdesk Response presents an overview of curriculum reform implementation within the context of Covid-19 and strengthening education systems for when children return to school ('building back better'). The document emphasises interventions and evidence relevant to African countries.
ZenodoArchiveID: 5652087 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3470024 10.5281/zenodo.5652087 2339240:69J5ZJAK 2405685:L3P7EL3U 2405685:TEL4GR8G
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Overview of emerging country-level response to providing continuity under COVID-19 What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (EdTech Hub, 2020)
Summary of report Scope of study This report provides a rapid summary of country-level responses to the management of school closures in 2020, with a focus on the needs of disadvantaged students and the role of technology. We consider low-income, middle-income and high-income countries. • We take a broad view of …
ZenodoArchiveID: 4707782 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707782 2405685:G647DH86 Library Catalog: edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted; _zenodoETH

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
ZenodoArchiveID: 4895400 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4895400 2339240:F8IYBAPY 2405685:57DYPNLR 2405685:DR6BDMJS 2405685:PTC9PGZW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

Value for Money Policy and Procedure - EdTech Hub (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:DLHKFUVC 2405685:V6TUMYRQ

Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
ZenodoArchiveID: 4706076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706076 2339240:XWBHC8ID 2405685:CD9IAPFX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Monitoring and evaluating radio in education - McBurnie, Chris (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707898 2129771:E77BS5IR 2405685:PLW5MPU5
Keywords: _EdTechHub_Output; dode_eth-src-eth; dode_eth-trf2-dode

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education — home page - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, 2020)
ZenodoArchiveID: 4684355 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684355 2339240:29LWMJ9W 2339240:FE9TLJQM 2405685:AX8D5YK2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Nine takeaways from our reviews of COVID-19 education responses - Chuang, Rachel; Kaye, Tom; Koomar, Saalim; McBurnie, Chris; Moss Coflan, Caitlin (EdTech Hub, 2020)
Regular readers will know about our Helpdesk, the on-demand support service we provide for FCDO advisers and World Bank staff to help them make evidence-informed decisions. Since the onset of coronavirus, the Helpdesk team has responded to requests from 15 countries across Africa, Asia, and the Middle…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707876 2405685:28EHRZSK
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Distance Learning as a Tool for System Resilience - EducationLinks (2020)
Find related information on EducationLinks at https://www.edu-links.org/events/dist.... COVD19 has had an unprecedented impact on educational systems across the world and required school systems to pivot to remote learning in mass. This panel discussion webinar explored the lessons learned, opportunities and challenges presented by this shift, and identified ways that distance learning modalities can continue to contribute to making educational systems more flexible, adaptable and inclusive of students who may be poorly served by traditional models. Experts from EDC, EdTech Hub, WorldReader and USAID/Egypt shared their insights on how distance learning can strengthen educational outcomes for students across the sector. This event was part of the Global Education Learning Series, learn more about the series at https://www.edu-links.org/LearningSeries
ZenodoArchiveID: 4706933 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706933 2339240:4WU2C356 2405685:4PVHDPR5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodoETH

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4645807 10.5281/zenodo.4728174 2405685:552YTW72 2405685:BBWJNPNA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
ZenodoArchiveID: 4460344 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4460344 2129771:DDU3QPXM 2339240:5XNMEGSN 2339240:XIRCF4HG 2339240:XXL72KUQ 2405685:2QM825CH 2405685:5RMUBA3Q 2405685:GBS5KW7S
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Strategy for Tanzania — Focus Area: TCPD in primary schools - El-Serafy, Yomna; Khalayleh, Abdullah; Carter, Alice; Haßler, Björn; Proctor, Jamie; Adam, Taskeen (EdTech Hub, 2021)
ZenodoArchiveID: 4742727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4742727 2405685:BPHSJBH7
Keywords: _EdTechHub_Output

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4279156 10.5281/zenodo.4279156 2129771:XYEJSVYW 2339240:59XYS4NB 2339240:EETQSD8S 2339240:HZTGKNN9 2405685:2W6A2G3H 2405685:6KDDB8UA 2405685:MS5GH9KJ 2405685:S9MFQ8KB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory with country statistics - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Khalayley, Abdullah; McBurnie, Chris; McIntyre, Nora (EdTech Hub, 2020)
Keyword inventory with country statistics (Updated July 2020)
EdTechHub.Copy: 2129771:ACGUWMNN EdTechHub.Copy: 2129771:ACGUWMNN KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3908363 2129771:ACGUWMNN 2339240:BFHYXP48 2405685:55A44ZRB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:s; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
ZenodoArchiveID: 3469739 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3469739 2129771:IGCN5KBD 2339240:4DKQGFTT 2405685:25G275PG 2405685:L5TMC4NJ 2405685:YRC7UKWE
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

A mixed-methods evidence assessment for emergent fields of knowledge - Haßler, Björn (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4698915 PreviousDOI: 10.5281/zenodo.4698915 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4698915 10.53832/edtechhub.0003 2129771:E3W7NXR9 2405685:PUVVR28E
Keywords: _EdTechHub_Output; _yl:m

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Refugee education: The crossroads of globalization - Dryden-Peterson, Sarah (Educational Researcher, 2016)
In this article, I probe a question at the core of comparative education—how to realize the right to education for all and ensure opportunities to use that educ...
KerkoCite.ItemAlsoKnownAs: 10.3102/0013189x16683398 2339240:VI7UJX9B 2405685:BA7Y334L
Keywords: AA - to delete; Edtech hub/ refugees education

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, 2020)
Education for the most marginalised post‑COVID-19 Guidance for governments on the use of digital technologies in education Join us December 18 for the report launch! Click here to register. The UNESCO Chair in ICT for Development, with support from the EdTech Hub, developed this report and associated Guidance Notes in 2020 building on a series of regional and sectoral consultations…
KerkoCite.ItemAlsoKnownAs: 2339240:IK5SDRGN 2339240:JTDGHA3K 2405685:D22ZXDPG 2405685:UNZYXGC6
Keywords: ___working_potential_duplicate

Guidance Note Introduction From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684349 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684349 2339240:NWU5LWKN 2405685:HB9A9YJE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Using Blended Learning to Support Marginalised Adolescent Girls’ Education: A Review of the Evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
This topic brief reviews evidence about the use of blended learning to support the education of marginalised adolescent girls in low- and middle- income countries.
ZenodoArchiveID: 4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.3952069 10.5281/zenodo.3952069 2405685:7PYD5JNV 2405685:H3AI5F3C 2339240:ENEKVCE3 2129771:FX6TFDPQ 2129771:9Q4PMCJN 2486141:TE93MW3V KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952069 10.5281/zenodo.4762319 10.53832/edtechhub.0009 2339240:MU9RJZS3 2339240:WG969BFI 2405685:7PYD5JNV 2405685:A7IA7VZZ 2405685:H3AI5F3C 2405685:XMDKD3TS
Keywords: F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Education for the most marginalised post-COVID-19: Guidance for governments on the use of digital technologies in education – Act one - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684287 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684287 2339240:EXUHD2R4 2405685:VFERK5JK
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Zero-Rating Educational Content in Low- and Middle-Income Countries - McBurnie, Chris; Adam, Taskeen; Kaye, Thomas; Haßler, Björn (EdTech Hub, 2020)
ZenodoArchiveID: 3784940 previousshortDOI: 10/gg7sqj previousshortDOI: 10/gg7sqj previousDOI: 10.5281/zenodo.3784940 previousshortDOI: 10/gg7sqj EdTechHub.Copy: 2129771:4W3D35BT EdTechHub.Copy: 2129771:4W3D35BT shortDOI: 10/gg7sqj KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3784940 10.53832/edtechhub.0004 10/gg7sqj 2129771:4W3D35BT 2339240:7VJMDZGM 2339240:RSJNXIC6 2405685:DX5RMV6U 2405685:F4PCMTZB
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2020)
In March 2020, many countries began to close schools to slow the spread of coronavirus. Education leaders have subsequently launched rapid response programmes, implemented measures to support system recovery and explored long-term reforms. This paper proposes a five-part approach to guide education leaders through this process.
ZenodoArchiveID: 3756012 previousDOI: 10.5281/zenodo.3756012 EdTechHub.Source: 2405685:JLEWADHF EdTechHub.Source: <this> KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3756012 10.53832/edtechhub.0005 2129771:SB3DJ28L 2129771:XKGV4EYL 2339240:5FRH2GYG 2339240:97HNYI75 2339240:S82QHGKQ 2405685:JLEWADHF 2405685:JTYIWEJY 2405685:L8KCID8V 2405685:NLEUNMRZ 2405685:SCDLVVC7 2405685:YMZUYZ4Z 2486141:9MWJP6MS
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:i; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Why the COVID Crisis Is Not EdTech’s Moment In Africa [repost] - CrawFurd, Lee (Open Development & Education, 2020)
With schools closed for hundreds of million students around the world, many have hoped that “edtech” can help keep children learning via internet, apps, and mobiles. A new database published by the EdTech Hub shows that though use of edtech products serving African countries has doubled in the last month, the total number of users is still very low, and most were viewers of one TV show. That, coupled with the fact that most firms come from just a few countries, suggests that edtech in Africa is far from maturity.
Library Catalog: opendeved.net KerkoCite.ItemAlsoKnownAs: 2339240:HPBQVQHE 2405685:DKQNMNM9 2405685:YRLJ3A6U

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2405685:2J7K7DAQ 2486141:3ILITC56

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
EdTechHub.Source: 2129771:MIMJJLN9 shortDOI: 10/ghgk6t KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3753513 10.5281/zenodo.4706085 10/ghgk6t 2129771:AS5ALSKL 2129771:MIMJJLN9 2339240:742PGZ2D 2405685:36KIX7YE 2405685:5IMAIVQY 2405685:696M6DK9 2405685:RAAGIU4Q
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
ZenodoArchiveID: 4706062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706062 2339240:IB8GIAAB 2339240:VEARRJJL 2339240:XRVLW2AX 2405685:BR48DF69 2405685:IPAT355N 2405685:SDTIZDHS
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Teacher Deployment in Sierra Leone: Lessons learnt and moving forward - Beoku-Betts, Iman (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0145 2405685:WVRHTVIZ 2486141:V94NMZIU

Mapping national digital learning platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo. (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0109 2339240:Q5SA4ZF4 2405685:T3BBADG2
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0069 2339240:DSE6SQXN 2405685:JAQWKTM3

Developing a teacher-focused theory of change for technology-enhanced teaching and learning - EdTech Hub Team (2021)
Internal Brief
KerkoCite.ItemAlsoKnownAs: 2405685:2SL6PDSS

17 EdTech Frameworks and Who Needs to Know Them - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam; Wilson, Susan Nicolai, Christina Myers, Arnaldo Pellini, Namrata Sharma and Sam, Akanksha Bapna (EdTech Hub, 2021)
17 EdTech frameworks that provide a valuable bridge between theory and practice. EdTech resources for policy-makers, educational institutions, teachers and multi-stakeholders.
KerkoCite.ItemAlsoKnownAs: 2339240:ZT8D763J 2405685:9TG8YM2I

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
previousDOI: 10.5281/zenodo.4762301 previousDOI: 10.5281/zenodo.3873462 EdTechHub.Copy: 2129771:237CSM4W EdTechHub.Copy: 2129771:237CSM4W KerkoCite.ItemAlsoKnownAs: 2129771:237CSM4W 10.5281/zenodo.3873462 10.5281/zenodo.4762301 10.53832/edtechhub.0007 2129771:237CSM4W 2129771:RMWSKUI5 2339240:2Y5CD84V 2339240:4P99D7MN 2339240:5P9STQIK 2339240:8DMB3N8E 2339240:AQFSE6DQ 2339240:K3RVT7JU 2339240:WP59YJ57 2339240:ZV7A4BWS 2405685:3T894KD8 2405685:3TKLS2TH 2405685:3UXB7ZWR 2405685:BHY8AJBY 2405685:I62EYSDT 2405685:LNUMVYFV 2405685:P5MEX8KB 2405685:R9VVKUH5 2405685:T48HFJM4 2486141:IX4B74H9 2534378:T2X9U5AV
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Focus country: Bangladesh - EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R62Y25DW 2405685:IFIR3QC9

Education system management / EMIS / education data – EdTechTools - EdTech Hub (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:YGEJ34XE 2405685:GTJ3R8F6 4656463:ZZTLJD2P

Engaging parents and caregivers in EdTech is critical to foundational learning in Kenya - Nicolai, Susan; Khan, Amina; Mwachi, Joan; Otieno, Jennifer Cotter (EdTech Hub, 2022)
Kenya, sometimes called the ‘Silicon Savannah’ of Africa, is home to one of the most vibrant EdTech ecosystems in Africa (see Otieno & Taddesse, 2020). Building on government initiatives such as the flagship Digital Literacy Programme (DLP), the country’s Covid-19 education response (Ngware & Ochieng, 2020) included tremendous efforts to provide distance learning solutions. This week, the Kenya EdTech Summit 2022 is bringing together many of those who have been making this happen to discuss the role of evidence and collaboration to accelerate the pace of progress in Kenya.
KerkoCite.ItemAlsoKnownAs: 2339240:FP2F79YV 2405685:BLIUPRZV

Reimagining Education for Continuous Learning and Teaching - Sengeh, Hon Minister David Moinina; Team, MBSSE Delivery; Team, Hon Minister David Moinina Sengeh and MBSSE Delivery (EdTech Hub, 2021)
EdTech Hub has partnered with the Ministry of Basic and Senior Secondary Education in Sierra Leone to increase the use of evidence in decisions around EdTech. Click to read more.
KerkoCite.ItemAlsoKnownAs: 2339240:6JKPNDHR 2405685:SQ7GPXQJ

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0105 2339240:36ZMGZUW 2405685:AWVEAJGC
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Digital Learning Solutions | Digital Learning For Every Child - Giraldo, Juan Pablo; Tungatarova, Auken; Cooper, Rachel (EdTech Hub, 2021)
UNICEF and EdTech Hub are partnering together to improve learning outcomes through effective uses of EdTech and digital learning. Read this guest post from UNICEF team members which focuses on the first pillar of UNICEF’s Reimagine Education initiative, world-class digital learning solutions.
KerkoCite.ItemAlsoKnownAs: 2339240:CF8CHKIM 2405685:9WZQKU59

Reading Audrey Watters: A reflection on personalised learning via education technology through a decolonial lens - Sarwar, Moizza Binat (EdTech Hub, 2022)
At EdTech Hub, we’ve been reflecting on how coloniality is embedded in the work we do: from the colonial roots of the international development sector, to colonial practices embedded in research methods, to “core-to-periphery” design and deployment of EdTech interventions.
KerkoCite.ItemAlsoKnownAs: 2339240:7LCXLE8L 2405685:U3M7PGEE

Designing and monitoring distance teaching and learning interventions: A guide for projects and implementers - Girls' Education Challenge; Fund Manager; EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:58CZ6GI8 2405685:ATJRX6DV

Why East Africa’s education systems must build climate resilience now: Three takeaways from a conference - Mbugua, Ciku; Simmons, Hannah; Barretto, Johnpaul; Barretto, Hannah Simmons and Johnpaul, Ciku Mbugua (EdTech Hub, 2024)
How can education systems build resilience to climate change? EdTech Hub explored this critical question at the inaugural East African Community Education Conference, held in Arusha this August. Discover our key insights in this blog.
KerkoCite.ItemAlsoKnownAs: 2339240:8JH5JWWD 2405685:3697CB4V

Using technology to support teacher continuous professional development in Sierra Leone - Beoku-Betts, Iman; Plaut, Daniel; Tanweer, Rabia; Tanweer, Daniel Plaut and Rabia, Iman Beoku-Betts (EdTech Hub, 2022)
In Sierra Leone, EdTech Hub has been working closely with the TSC and the World Bank over the last 18 months to design a TCPD model that will provide primary school teachers with tools to improve their literacy and numeracy instruction.

First Lessons from Our Study: Optimising Messaging for Returns to School - Kably, Nathan; Mitchell, Joel; Zhao, Annette; D'Rozario, Jonny (EdTech Hub, 2023)
This blog examines the valuable insights gained from EdTech Hub's initial research on the use of messaging (primarily text messaging) to assist caregivers in promoting their children's school attendance. In this blog, we delve into the workings of messaging mechanisms and share our study findings. Additionally, we outline critical considerations for those interested in developing a comparable intervention. Read on to learn more...
KerkoCite.ItemAlsoKnownAs: 2339240:4T3GP6TA 2405685:IQRXCPLV

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
ZenodoArchiveID: 4705909 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705909 2339240:7ZRTPCRD 2339240:QN533HVR 2339240:SU542298 2405685:2HZ9V7IF 2405685:4CKXCNC2 2405685:9JB5M3HI 2405685:BAEUEWI9 2405685:CY5UL3B9 2405685:E3GHWHIZ 2405685:WXF7VILV
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Bibliography on teacher distribution and allocation - Haßler, Björn (2021)
ZenodoArchiveID: 4608425 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4608425 2339240:2DAZHLTB 2405685:WX9A6Z7X
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; dode_eth-src-eth

All Programmes Recorded, All Outputs Reported - Haßler, Björn; Adam, Taskeen; Blower, Thomas; El-Serafy, Yomna; Kaye, Tom; Khalayleh, Abdullah; McBurnie, Chris; Megha-Bongnkar, Ghislaine; Regis, Callista (EdTech Hub, 2021)
previousDOI: 10.5281/zenodo.4698917 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4698917 10.53832/edtechhub.0050 2129771:WSQ43VG8 2405685:VJYXV8JP
Keywords: AuthorFirst:Haßler; _yl:q

Usability Testing of a Mobile-based Learning Management System for Teacher Continuous Professional Development in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Haßler, Björn; Proctor, Jamie; EdTech Hub (The International Journal of Education and Development using Information and Communication Technology, 2023)
The last two decades have seen the growing adoption of mobile devices to enhance the quality of teachers' continuous professional development (TCPD) in low-income countries. Using mobile devices, typically not designed for educational use, presents new usability challenges, preventing teachers from effectively accessing learning materials in learning management systems (LMS). Therefore, it is important to test usability to improve the delivery of TCPD via mobile devices. This study evaluated the usability of TCPD-focused mobile-based LMS accessed via a mobile web browser and mobile app. The evaluation used a hybrid think-aloud method involving 63 teachers from 12 schools in Tanzania. Half of the schools were evaluated using a concurrent think-aloud method, and the other half using a retrospective think-aloud method. The study found that teachers encountered many usability problems in using the mobile app compared to those who accessed the LMS via mobile web browsers. The study also found usability flaws in the registration and login process, poor language translation, technical errors, and issues with quiz questions. These findings show the importance of user testing, even for well-developed LMS, such as Moodle. Additionally, this work provides useful guidance for those who want to implement mobile learning via an LMS in low-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:ZTWSB6CB 2405685:L5AY2YZI
Keywords: ⛔ No DOI found

Remote Learning: Rapid Evidence Assessment - Education Endowment Foundation (Education Endowment Foundation, 2020)
This rapid evidence assessment aimed to investigate methods that schools could use to support remote learning during school closures caused by the 2020 coronavirus pandemic (Covid-19). The review sought to find the best evidence behind the wide array of approaches that schools might choose to use during the crisis. The review systematically searched for/through existing meta-analyses and systematic reviews to find the best evidence for a wide range of approaches. In addition to the direct teaching of pupils online by teachers, the review also found evidence for approaches that pupils can use independently, including with technology that adapts the content of tasks in order to provide additional challenge or support, educational games, and for approaches that support peer interaction. The review also examined blended learning approaches, which combine remote and classroom teaching. While these approaches may not be directly applicable during school closures, they were included in case there were useful lessons to be learned that were relevant to the current context of home learning. This report summarises the findings from 60 systematic reviews and meta-analyses answers under five key topic areas: - General remote teaching and learning - Blended learning - Computer-supported collaborative learning - Computer assisted instruction - Educational games Another crucial aspect of supporting pupil’s learning is parental engagement. Parental engagement approaches are beyond the scope of this review, but an existing EEF guidance report, Working with Parents to Support Children’s Learning (2019), and accompanying evidence review summarise the best available evidence for engaging parents in their children’s education. In each section, we have detailed the included reviews and listed Findings and implications drawn from the evidence. We have also highlighted case studies from projects funded by the Education Endowment Foundation in which similar approaches have been rigorously evaluated in English schools.
ZenodoArchiveID: 4477023 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4477023 2259720:VZ7YJUFN 2339240:85V26WNW 2339240:HGMUANP7 2339240:JIW4TDS5 2339240:VJ8WRVRV 2405685:8ASGAE9Q 2405685:B3K7PU24 2405685:GPMMTF99 2405685:HCC97T3B 2405685:LW2NDPNQ 2405685:V3SZZR28
Keywords: Methods; _DOILIVE; _EdTechHub_Output; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Online and distance teaching and learning A32ARSFK; _cover:other:ok; _zenodo:submitted; _zenodoETH

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.
KerkoCite.ItemAlsoKnownAs: 2405685:WVVB6PCG

Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs - McIntyre, Nora; Sabates, Ricardo; Jamieson Eberhardt, Molly (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:BJT3BKFR 2405685:V9FUFGLQ

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Pacitto, Julia; Barnes, Katrina; Mukankusi, Aimée; Zazai, Rozina (EdTech Hub, 2023)
This article presents the ﬁndings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Ofﬁce (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identiﬁes the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls.
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0172 2339240:IH7X7TBE 2405685:BCNUTSXS

When teachers are asked to deploy other teachers, we learn a lot about teacher preferences - McBurnie, Chris; Godwin, Katie; Bernard-Jones, Lydia (EdTechHub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6412386 2339240:YGGYBFB6 2405685:BPUZD5T5 2405685:EZZ3QXCT 4656463:W4SE8RSY
Keywords: _r:AddedByZotZen

Designing for scale: Learnings from a design-based research study of a technology-based personalised learning mathematics platform - Bapna, Akanksha; Myers, Christina; Sharma, Namrata (2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7100019 ZenodoArchiveConcept: 7100018 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7100019 2405685:NUAAR9IR
Keywords: _r:AddedByZotZen

Keeping Kenya Learning: The importance of caregiver engagement in supporting learning beyond the classroom - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Since the Covid-19 pandemic began, parents, teachers, students and policymakers have been exploring how to support students to learn at home. The emphasis on education at home has made evident the need to better equip caregivers to support their children’s learning. The Keep Kenya Learning (KKL) initiative is helping parents and caregivers build their capacity and confidence to support learning…
KerkoCite.ItemAlsoKnownAs: 2405685:LZM9KHE6
Keywords: _EdTechHub_Output

Hybrid learning: International experiences with multimodal approaches - Villavicencio, Xuzel; Coflan, Caitlin (2022)
This slide deck was originally developed for a webinar series on blended and hybrid learning for UNICEF El Salvador and the El Salvador Ministry of Education. The online workshops were delivered in two sessions, with the teachers from El Salvador as a key part of the audience. Along with the lessons learnt from the various international initiatives mapped, subjects like the country's ICT infrastructure and the relevance of a Socio Emotional Learning (SEL) approach were also covered. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; socio-emotional learning. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023344 ZenodoArchiveConcept: 7023343 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023344 10.53832/edtechhub.0112 2405685:C2SK9SF9
Keywords: _r:AddedByZotZen

Aprendizaje híbrido Experiencias internacionales con enfoque multimodal - Villavicencio, Xuzel; Coflan, Caitlin (2022)
Esta presentación se elaboró originalmente para una serie de seminarios web sobre aprendizaje blended e híbrido para UNICEF El Salvador y el Ministerio de Educación de El Salvador. Los talleres en línea se impartieron en dos sesiones, con los profesores de El Salvador como parte fundamental de la audiencia. Junto con las lecciones aprendidas de las diversas iniciativas internacionales mapeadas, también se tocaron temas como la infraestructura de las TIC del país y la relevancia de un enfoque de Aprendizaje Socioemocional (SEL). Keywords: híbrido; blended; multimodal; El Salvador; capacitación docente; aprendizaje socioemocional An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6981609 ZenodoArchiveConcept: 6981608 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6981609 10.53832/edtechhub.0113 2405685:G8RZFT8Z
Keywords: _r:AddedByZotZen

Unlocking Literacy: Navigating Parental Engagement with Worldreader’s BookSmart in Kenya - Smith, Wendy; Nicolai, Susan; Kartha, Ashwati; Kimani, Olivia (EdTech Hub, 2024)
Globally, just one-third of 10-year-olds can read and understand basic written stories. Can EdTech and parental engagement change this? Read on to learn more.
KerkoCite.ItemAlsoKnownAs: 2339240:IVVWJ3JN 2405685:9GPPW9T2

GIS for Education Working Group - the Education Commission (the Education Commission, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:PEEHJ6D6 2405685:6NKZST4H
Keywords: _yl:a

Disseminating the Evidence and Outputs Generated by Your Programme: Three options for setting up an evidence library - Haßler, Björn; Mansour, Hassan; Friese, Laila; Longley, Sophie (EdTech Hub, 2024)
This document is designed as a guide for building and implementing a content management system, specifically an evidence library, prioritising the needs of research programmes generating evidence for other researchers and policymakers and for public readership and global dissemination. The primary focus is on securely building a system to meet research discovery requirements, such as search engine optimisation, and visibility on Google Scholar. A robust content management system like an evidence library goes beyond simply meeting web standards. It is about enhancing the research discoverability of your work, gauging your impact and reach, increasing the accessibility of your evidence, and fostering a more collaborative environment. This comprehensive approach is vital for successfully sharing evidence with the public and the global community. The document is primarily aimed at project or communications leads. We assume no specific technical expertise. It seeks to help you decide how to deploy an evidence library and whether to draw on internal or external resources (such as web developers). We expect the document to also be useful for product owners and web developers; however, we expect that for such users, the document will cover a lot of familiar ground. Keywords: evidence library; dissemination; data; research; share; content; management
ZenodoArchiveID: 10114341 ZenodoArchiveConcept: 10114340 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1001 2405685:PWN42VDQ
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
ZenodoArchiveID: 5652141 previousDOI: 10.5281/zenodo.4762283 previousDOI: 10.5281/zenodo.4762283 2405685:UQSMRFBF previousDOI: 10.5281/zenodo.3407498 EdTechHub.Source: DOI: DOI:10.5281/zenodo.4762283 2405685:UQSMRFBF EdTechHub.Source: <this> shortDOI: 10/ghgnd8 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407498 10.5281/zenodo.5652141 10/ghgnd8 2129771:U3XSZB5F 2339240:CRCGCNE9 2405685:UQSMRFBF
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

SWOT Analysis of the Kenya Education Cloud - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
ZenodoArchiveID: 4745991 prevDOI: 10.5281/zenodo.4486279 prevDOI: 10.5281/zenodo.4742327 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4486279 10.5281/zenodo.4742327 10.5281/zenodo.4745991 2129771:LSCJ2AJX 2339240:95YP93VL 2339240:PBZKVTI5 2339240:WW642LX9 2405685:R3E3KVHX 2405685:TAWFGNE2 2405685:UMJTLGUE
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _cover:v3; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Five ways geospatial analysis can help visualize and solve some of education’s biggest challenges - the Education Commission (the Education Commission, 2021)
As the education community continues to mobilize efforts towards achieving Sustainable Development Goal 4 (SDG 4), stakeholders at all levels of the system are grappling with questions on how to deliver inclusive quality education. What communities will benefit most...
Section: Updates KerkoCite.ItemAlsoKnownAs: 2129771:QDUZU3YQ 2405685:2ST897UD
Keywords: _yl:c

GIS for Education Working Group launches to promote data-driven decision-making - the Education Commission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Section: Updates KerkoCite.ItemAlsoKnownAs: 2129771:5XRHZSJ4 2405685:FJZKNYJI
Keywords: _yl:b

Best Practice in Pedagogy for Remote Teaching - McAleavy, Tony; Gorgen, Kristine (Education Development Trust, 2020)
ZenodoArchiveID: 4705039 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705039 2339240:DYB6DZ4Z 2339240:XMUK9UCI 2405685:4VZQDWNN 2405685:CKA82YZA 2405685:T4MVFPEL 2405685:X4GWSACH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found; ⛔ No INSPIRE recid found

OU part of £5.5m research portfolio to improve education tech in low and middle income countries - Grimette, Hannah (OU News, 2022)
The Open University (OU) has launched a study with global research partner, Edtech Hub, to investigate the impact of technology on teaching in Bangladesh. Part of EdTech's first research portfolio, the OU's 3Mpower is one of 13 projects, which represents the largest investment in primary research on EdTech's use in low- and middle-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:M5XGVS2H 2405685:EXXQ3R4B

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707808 2405685:PBKNDCEU
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Making innovation work for girls and women in Tanzania, Tanzania: HDIF, 2017 - Bangser, Maggie; Davies, Emma; Lähde, Kristiina; McGinty, David (HDIF Tanzania, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZALEY47R 2405685:T32KPMWC

Teacher educators and OER in East Africa: Interrogating pedagogic change - Wolfenden, Freda; Auckloo, Pritee; Buckler, Alison; Cullen, Jane (Adoption and Impact of OER in the Global South, 2017)
This study examines the use of Open Educational Resources (OER) in six teacher education institutions in three contrasting East African settings – Mauritius, Tanzania and Uganda – all of which had previous engagement with OER initiatives. Drawing primarily on interviews with teacher educators, the study examines how and when teacher educators engage with OER, the factors that support and constrain sustained OER engagement, and the influence of such engagement on their teaching practice. It seeks to answer the following three research questions: What kinds of OER are teacher educators aware of and how do they access them? How and for what purpose are they using the OER? What intended and enacted pedagogic practices are associated with OER use? The study takes a sociocultural approach, paying attention to the practices of teacher educators and the context and culture of the teacher education institutions within which they work, as well as the national policies relevant to these institutions. Surveys were sent to academic staff at each of the participating institutions who were, or had been, involved in curriculum development work involving OER. Male and female educators from different disciplinary backgrounds and with varying roles and periods of service within the institutions were targeted. From the respondents, selected individuals were asked to participate in semi-structured interviews concerning OER and their pedagogical practices. A total of 58 surveys were completed by teacher educators along with 36 in-depth teacher educator interviews and six institutional stakeholder interviews. The results of the study indicate that teacher educators’ understanding and use of OER is highly fragmented, with little traction at department or institutional level. At all the study sites there was dissonance between the ways in which individual educators are using OER and the dominant institutional values and discourse. There were also numerous structural and cultural factors acting to limit agency with regards to OER use. The demands of curriculum and assessment, professional identity, digital skills, provision of equipment and connectivity, values and weak cultures of collaboration all exerted an influence and enabled or constrained teacher educators’ efforts to achieve agency with OER. For a small number of teacher educators (OER “champions”), OER provides a tool for extending their agency to move towards more participatory practices. In their interviews, several of these educators spoke of the formative role of academic training and many were linked to external OER networks. These elements of historic identity formation influence how they respond to OER, and enhance their confidence to take risks in moving beyond conventional practice. Enabling educators to act in an agentive way with OER is not easy. Moving forward, attention should be given to issues of access so that educators are able to locate and view OER relatively easily and experiment with their use. This study recommends that time be made available for educators to enhance their skills in working digitally and to become familiar with principles of learning design such that these become integral dimensions of their professional identity. It is also argued that extending and deepening engagement with OER requires opportunities for professional dialogue and collaboration to support the development of productive educator identities with OER and transformation of the community’s field of practice.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1094850 2339240:CV3YAJZ6 2405685:T9JSZ9PS
Keywords: East Africa; Global South; Mauritius; OEP; OER; Open Education; Open Educational Resources; ROER4D; Tanzania; Uganda; _not_EdTechHub; _zenodoOTHER; agency; pedagogy; teacher education

Tanzania 2017 field testing report: Can out-of-school children make learning gains with Kitkit School? - Kitkit School (Kitkit School, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:X5YJZY69 2405685:BNM2LVRY

The Storytelling Project Handbook - Dixon, Miranda; Patuck, Lil (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5Y3NRH26 2405685:TJTKAKJD

Jusoor’s WhatsApp-Assisted Learning Programme: Sprint Review 1. - Tutunji, Suha; Boujikian, Michèle; Carter, Alice; Atkinson, Grace (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:G5RD3H5K 2405685:NBWSSFLK
Keywords: ___working_potential_duplicate

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.
Num Pages: 18 Publication Title: ActionAid KerkoCite.ItemAlsoKnownAs: 2339240:4FGB56K3 2405685:53CECDLI

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3906041 10.5281/zenodo.3906041 2339240:35NW4SYR 2405685:VD8J4NCU

Girls' education and COVID-19 in Pakistan - Malala Fund (Malala Fund, 2020)
In Girls’ education and COVID-19 in Pakistan, Malala Fund and our Education Champions highlight the impact of school closures on students in all four provinces with an emphasis on girls’ experiences.
KerkoCite.ItemAlsoKnownAs: 2339240:DG6S3PKT 2339240:K7LBRSIU 2405685:53NXWVMN 2405685:AYKYWR8J

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Archive: https://zenodo.org/record/4817787 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 10/gj6k5n 2339240:382K6GCA 2339240:53R3ZYT5 2339240:CYQPAERV 2339240:EXFAZMDQ 2339240:P2I2EU98 2339240:RM59PWFE 2405685:5U948655 2405685:FIXCCB5I 2405685:HBGSTQ7X 2405685:QFTDGH3C 2405685:RZNJVMWH 2405685:V8UFGT52 2405685:WTT4UQ43 2405685:ZD4YGMMJ 4042040:G8KVDVSC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:6FQK6S4F 2339240:NF2Q8AEW 2405685:7J38238R
Keywords: ⛔ No INSPIRE recid found

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JUGDD7MG 2405685:CYTW2JQW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Out-of-School Children and Youth in Southeast Asia: A Rapid Scoping Study - Afzal, Nimra; Barnes, Katrina; Hayat, Amal; Mazari, Haani; Jayasinghe, Neema; Sentillas, Emil (2024)
This rapid scoping study has been conducted by EdTech Hub and the Southeast Asian Ministers of Education Organization (SEAMEO) Secretariat through the ASEAN-UK Supporting the Advancement of Girls Education (ASEAN-UK SAGE) programme. Through the ASEAN-UK SAGE programme, secondary research has been conducted on the current situation of out-of-school children and youth (OOSCY) in Southeast Asia by Dabrowski et al. (2024) and Barnes et al. (2024). Building on these efforts, this study provides an updated and nuanced overview of the reasons for children and youth in the region being out of school and the policies and programmes that support them. The study used new primary data generated by surveys with education actors and interviews with OOSCY, their caregivers, and teachers, combined with a review of existing documentation. It is important to note that this study is deliberately high level, as it seeks to provide a snapshot of the OOSCY situation in the region as a whole. The findings should therefore be considered indicative rather than comprehensive, and deeper, country-specific profiling, analyses and targeted recommendations will be provided through forthcoming country case studies and thematic papers.
KerkoCite.ItemAlsoKnownAs: 2339240:P48KHC6J 2405685:5F5HC2M4

What we are learning | What we are reading: Digital Personalised Learning – How can technology be used to maximise the effectiveness of personalised learning and teaching at the level of the student? - Mazari, Haani (EdTech Hub, 2022)
Significant financial resources are being invested in a wide range of DPL programmes, but there is no clear evidence on whether they are more effective as a complement or substitute to other learning content and how they might be used in low- and middle-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:2LUSU3T7 2405685:CN4WCIB5

Innovative Methods to Train Teachers of Blind Children - Kibet, Amon; Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Discover what we learned using innovative methods such as virtual training via WhatAapp to train teachers of blind children. Click to read more.
KerkoCite.ItemAlsoKnownAs: 2339240:ULNM6MVY 2405685:9872JIDA

The Importance of Caregiver Engagement in Supporting Learning - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Do you know the importance of caregiver engagement in supporting learning beyond the classroom? Visit our website to learn more.
KerkoCite.ItemAlsoKnownAs: 2339240:MCEFY3WR 2405685:7VZZBHDN

Scaling Personalised Learning Technology in Malawi - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.
KerkoCite.ItemAlsoKnownAs: 2339240:KWP37J8V 2339240:QWF5YPUM 2405685:3JNLR2A9 2405685:PMDAD9XJ

Where do teachers go, and where do they stay? - Lurvink, Anne-Fleur; Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alasdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn; Godwin, Katie; Godwin, Patricia Espinoza-Revollo, Yusuf Ali, Oliver Garrod, Paul Atherton, Alasdair Mackintosh, Ana Ramirez, Iman Beoku-Betts, Björn Haßler and Katie, Anne-Fleur Lurvink (EdTech Hub, 2023)
In Sierra Leone, a government payroll position is tied to the teacher, not the school, meaning teachers can change schools once they go on the payroll. This leads to certain schools being chronically understaffed. It also suggests that deploying teachers to rural and understaffed schools (or putting teachers already there on payroll) might not tackle high pupil-to-qualified-teacher ratios in the longer term. Investigating the school-to-school movement of payroll teachers can help us understand where teachers go after they go on the payroll and how long they stay in a given school. We also looked at overall movement nationally to identify areas of the country that are outliers in terms of high and low retention of teachers.
KerkoCite.ItemAlsoKnownAs: 2405685:LC8X4TCC

Evidence to Strengthen Tech-Supported Teacher Development in Madagascar - Coflan, Caitlin Moss; Koomar, Saalim; Rasolohery, Hasiniavo (EdTech Hub, 2021)
Our latest blog looks at using evidence to strengthen tech-supported teacher professional development in Madagascar. For more details, visit our website.
KerkoCite.ItemAlsoKnownAs: 2339240:ANDK8LBN 2405685:DRXSJH4U

MEWAKA in Tanzania: Emerging findings on tech-supported teacher professional development - Koomar, Saalim; Massam, Winston; Anthony, Gervace; Mrope, Winifrida; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fredrick; Proctor, Jamie; Komba, Aneth; Mwakabungu, Fika; Barretto, Johnpaul; Barretto, Winston Massam, Gervace Anthony, Winifrida Mrope, Taskeen Adam, Sara Hennessy, Fredrick Mtenzi, Jamie Proctor, Aneth Komba, Fika Mwakabungu and Johnpaul, Saalim Koomar (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teachers’ Continuous Professional Development (TCPD)) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The programme is decentralised, with teacher learning based in schools and focused on semi-structured Communities of Learning (CoLs). CoLs are spaces where teachers can gather weekly to discuss and reflect on issues most relevant to their schools as well as learn and improve their pedagogical skills. Peer facilitators help teachers to collaboratively solve problems, learn new approaches to improve their practice, and generally create a culture of reflection and school improvement.
KerkoCite.ItemAlsoKnownAs: 2339240:AQZAQSU7 2405685:KMN7H8UA

Access to and use of technology by primary school teachers: A survey in the 23 regions of Madagascar - Rasolohery, Hasiniavo; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2023)
The Madagascar Ministry of National Education, through the National Institute for Pedagogical Training, plans to use new technology in teacher training for early-stage reading and writing in Malagasy. This initiative is undertaken within the framework of the Madagascar Basic Education Support Project. The main objective is to train 5,000 teachers of the T2 class remotely, drawing inspiration from systems such as the Distance Education for Primary Teachers (FADEP).
KerkoCite.ItemAlsoKnownAs: 2339240:V4Z9QSPV 2405685:9NYHCGPM

Digital Personalised Learning to Improve Literacy and Numeracy Outcomes in Kenyan Classrooms - Daltry, Rebecca; Major, Louis; Sun, Chen; Otieno, Mary; Otieno, Kevin; Otieno, Louis Major, Chen Sun, Mary Otieno and Kevin, Rebecca Daltry (EdTech Hub, 2023)
This blog forms part of a wider research study on digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms, and outlines emergent findings from a randomised controlled trial following the first two rounds of assessment (baseline and midline). The preliminary findings will be strengthened after further analyses and endline assessment.
KerkoCite.ItemAlsoKnownAs: 2339240:SL5WSSVM 2405685:5BIU6BJ5

What we are learning | What we are reading: Digital Personalised Learning – How can technology be used to maximise the effectiveness of personalised learning and teaching at the level of the student? - Mazari, Haani (EdTech Hub, 2022)
Significant financial resources are being invested in a wide range of DPL programmes, but there is no clear evidence on whether they are more effective as a complement or substitute to other learning content and how they might be used in low- and middle-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:2LUSU3T7 2405685:CN4WCIB5

Access to and use of technology by primary school teachers: A survey in the 23 regions of Madagascar - Rasolohery, Hasiniavo; Koomar, Saalim; Mitchell, Joel; Mitchell, Saalim Koomar and Joel, Hasiniavo Rasolohery (EdTech Hub, 2023)
The Madagascar Ministry of National Education, through the National Institute for Pedagogical Training, plans to use new technology in teacher training for early-stage reading and writing in Malagasy. This initiative is undertaken within the framework of the Madagascar Basic Education Support Project. The main objective is to train 5,000 teachers of the T2 class remotely, drawing inspiration from systems such as the Distance Education for Primary Teachers (FADEP).

Scaling Personalised Learning Technology in Malawi: Lessons from our sandbox with onebillion - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.
KerkoCite.ItemAlsoKnownAs: 2339240:YWIIWQ2X 2405685:ZBHGFZXD

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7CKKU8RW 2405685:L43R48P2

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
A global survey of teachers’ responses to the Covid-19 pandemic
KerkoCite.ItemAlsoKnownAs: 2339240:L9HFYFBK 2339240:PG5K4YH4 2339240:VJ8NQRB8 2405685:452IQSGM 2405685:8993UPBX 2405685:SMFP44X2

Education for the most marginalised post-COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:DT5Q8T2B 2405685:JDSSXW7Q

Low-tech personalised learning to improve girls' education in Kenya. - Jordan, K; Damani, K; Khagame, P; Mongeau, C; Mumbi, A; Myers, C; Njuguna, L; Otieno, J; Zhao, A (EdTech Hub and M-Shule, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:M7HVSHJG 2405685:KN2IBMDV

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FY4BHGH3

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Keep Kenya Learning (KKL): Training to Engage Caregivers in Digital Learning - Keep Kenya Learning (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:B9P3SYV3 2405685:439ATWCE

A Dialogic Design-Based Research Partnership Approach: Developing Close-to-Practice Educational Technology Theory in Kenya - Major, Louis; Daltry, Rebecca; Rahman, Asad; Plaut, Daniel; Otieno, Mary; Otieno, Kevin (Global Perspectives on Teaching with Technology, 2024)
Design-based research (DBR) has promise for investigating educational technology in low- and middle-income contexts. However, DBR is implemented infrequently in such settings, highlighting a need for guidance on implementation. This chapter critically reflects on innovative DBR involving Kenyan teachers and research partners over two years. This focused on the iterative evaluation of a ‘digital personalised learning’ tool to improve its integration into classroom practice. This DBR promoted teacher-researcher engagement by adopting a dialogue-informed ‘intermediate theory building’ framework, bridging the theory-practice gap. Additionally, it enhanced inclusivity by broadening the concept of partnership through an ‘integrated’ approach. Lessons learned and practical implications are highlighted. Outcomes establish a novel foundation for applying DBR to enhance educational technology for marginalised learners.
Num Pages: 19 KerkoCite.ItemAlsoKnownAs: 2339240:ZWZ4VVZD 2405685:96RA5UW7 2405685:EJWQSZTI

CPD Implementation Roadmap - Cambridge Education (Cambridge Education, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:97LIFQ9D 2405685:APDWFXX2 2405685:AUN7ES7V